A deep-learning workflow to predict upper tract urothelial carcinoma protein-based subtypes from H&E slides supporting the prioritization of patients for molecular testing - Angeloni, Miriam; van Doeveren, Thomas; Lindner, Sophia; Volland, Patrick; Schmelmer, Jorina; Foersch, Sebastian; Matek, Christian; Stöhr, Robert; Geppert, Carol-Immanuel; Heers, Hendrik; Wach, Sven; Taubert, Helge; et al. (Journal of Pathology: Clinical Research, 2024)
Upper tract urothelial carcinoma (UTUC) is a rare and aggressive, yet understudied, urothelial carcinoma (UC). The more frequent UC of the bladder comprises several molecular subtypes, associated with different targeted therapies and overlapping with protein-based subtypes. However, if and how these findings extend to UTUC remains unclear. Artificial intelligence-based approaches could help elucidate UTUC's biology and extend access to targeted treatments to a wider patient audience. Here, UTUC protein-based subtypes were identified, and a deep-learning (DL) workflow was developed to predict them directly from routine histopathological H&E slides. Protein-based subtypes in a retrospective cohort of 163 invasive tumors were assigned by hierarchical clustering of the immunohistochemical expression of three luminal (FOXA1, GATA3, and CK20) and three basal (CD44, CK5, and CK14) markers. Cluster analysis identified distinctive luminal (N = 80) and basal (N = 42) subtypes. The luminal subtype mostly included pushing, papillary tumors, whereas the basal subtype diffusely infiltrating, non-papillary tumors. DL model building relied on a transfer-learning approach by fine-tuning a pre-trained ResNet50. Classification performance was measured via three-fold repeated cross-validation. A mean area under the receiver operating characteristic curve of 0.83 (95% CI: 0.67–0.99), 0.8 (95% CI: 0.62–0.99), and 0.81 (95% CI: 0.65–0.96) was reached in the three repetitions. High-confidence DL-based predicted subtypes showed significant associations (p < 0.001) with morphological features, i.e. tumor type, histological subtypes, and infiltration type. Furthermore, a significant association was found with programmed cell death ligand 1 (PD-L1) combined positive score (p < 0.001) and FGFR3 mutational status (p = 0.002), with high-confidence basal predictions containing a higher proportion of PD-L1 positive samples and high-confidence luminal predictions a higher proportion of FGFR3-mutated samples. Testing of the DL model on an independent cohort highlighted the importance to accommodate histological subtypes. Taken together, our DL workflow can predict protein-based UTUC subtypes, associated with the presence of targetable alterations, directly from H&E slides.
CRIS-Team Scopus Importer:2024-03-29
Keywords: deep-learning; digital pathology; immunohistochemistry; protein-based subtypes; targeted therapy; upper tract urothelial carcinoma; whole slide images

ALK -rearranged Mesenchymal Neoplasms With Prominent Foamy/Pseudolipogenic Cell Morphology : Expanding the Phenotypic Spectrum of ALK Fusion Neoplasms and Report of Novel Fusion Partners. - Agaimy, Abbas; Stöhr, Robert; Fisher, Cyril; Chrisinger, John S.A.; Demicco, Elizabeth G.; Tögel, Lars; Michal, Michal; Michal, Michael (American Journal of Surgical Pathology, 2024)
The category of ALK -rearranged mesenchymal neoplasms has been evolving rapidly, with reports of morphologically diverse lesions of cutaneous, soft tissue, and visceral origin. While some of these represent morphologically defined entities harboring recurrent ALK fusions (inflammatory myofibroblastic tumor and epithelioid fibrous histiocytoma), others are unclassified by morphology with variable overlap with the tyrosine kinase family of neoplasia and their underlying ALK fusions cannot be suspected based on morphology. We herein report 3 cases that expand the anatomic, morphologic, and genotypic spectrum of ALK -rearranged unclassified neoplasms. Patients were all adults aged 46 to 69 (median: 63) who presented with a mass located in the gingiva, subcutis of the back, and submucosal posterior pharyngeal wall. The tumor size ranged from 1 to 2.7 cm (median: 1.6). Conservative surgery was the treatment in all patients. Follow-up was available for one patient who remained disease-free at 14 months. Histologically, all tumors displayed large polygonal cells with foamy to granular and lipogenic-like microvacuolated copious cytoplasm and medium-sized round nuclei with 1 or 2 prominent nucleoli. Mitoses and necrosis were not seen. The initial diagnostic impression was PEComa, inflammatory rhabdomyoblastic tumor and unclassified pseudolipogenic neoplasm. Strong cytoplasmic ALK was detected by immunohistochemistry in all cases. Other positive markers include Cathepsin K (2/2), desmin (1/3), focal MyoD1 (1/1), focal SMA (1/3), and focal EMA (1/2). Targeted RNA sequencing revealed ALK fusions with exon 20 (2 cases) and exon 19 (one case) of ALK fused to RND3 (exon 3), SQSTM1 (exon 6), and desmin (intron 6). Methylation profiling in the desmin-fused case (initially diagnosed as inflammatory rhabdomyoblastic tumor) revealed an inflammatory myofibroblastic tumor match with a low confidence score of 0.5 and a flat copy number variation (CNV) profile. No NF1 mutation was detected in this case, altogether excluding an inflammatory rhabdomyoblastic tumor. Our study highlights and expands the morphologic and anatomic diversity of ALK- fused neoplasms and documents novel fusion partners ( RND3 and desmin).
EVALuna2:570327

ALK Rearrangements Characterize 2 Distinct Types of Salivary Gland Carcinomas Clinicopathologic and Molecular Analysis of 4 Cases and Literature Review - Agaimy, Abbas; Baneckova, Martina; Ihrler, Stephan; Müller, Sarina Katrin; Franchi, Alessandro; Hartmann, Arndt; Stöhr, Robert; Skalova, Alena (American Journal of Surgical Pathology, 2021)
The majority of salivary gland carcinomas are characterized by recurrent gene fusions that proved highly valuable diagnostically, but only rarely of therapeutic impact. Most of these fusion-positive carcinomas belong to the low-grade or intermediategrade biological category. To date, only 5 cases of salivary gland carcinomas carrying an oncogenic ALK fusion have been reported in 4 recent studies, but their phenotypic spectrum and their nosological classification remain uncharacterized. We herein describe in detail the clinicopathologic and molecular features of 4 ALK-fusion-positive salivary carcinomas and review previously reported cases to assess if they could be classified into a defined World Health Organization (WHO) category. Patients were 3 men and 1 woman aged from 67 to 79 years (median: 70 y). All tumors originated in the parotid gland. Their size ranged from 1.1 to 3 cm (mean, 2 cm). Three tumors were de novo high-grade salivary duct carcinomas (SDCs) and 1 was a low-grade intercalated-type intraductal carcinoma. Histologically, high-grade tumors were predominantly solid, composed of intimately admixed basal (CK5+, androgen-) and luminal (CK5-, androgen+) components. The remarkable basal component showed squamoid basophilic pattern imparting an adenosquamous-like appearance in all cases. Conventional apocrine intraductal high-grade carcinoma was noted in 1 case. Prominent intraductal growth of the solid basal component (highlighted by p63 staining) was seen in all cases. The tumor cells expressed CK7 (3/3), mammaglobin (3/3, 1 focal), GATA3 (3/3, 1 focal), variably CK5 (3/3), and focally the androgen receptor (1/3), but lacked expression of HER2/neu, SOX10, MUC4, TTF1, FS100, and Napsin A. The low-grade tumor showed classic histologic and immunophenotypic features of intercalated-type non-invasive intraductal carcinoma. Molecular profiling showed rearrangements involving exon 20 of ALK in all cases, confirmed by ALK immunohistochemistry (IHC and FISH). The fusion partner was EML4 (n= 2) and STRN (n= 1) in high-grade tumors and EML4 in the intraductal carcinoma. Two patients with high-grade tumors developed progressive disease (1 died at 9 mo; 1 alive under palliative therapy at 5 mo). This series and a review of 5 published cases indicate that ALK rearrangements characterize 2 distinct subsets of salivary gland carcinomas in the spectrum of high-grade androgen-poor, basal-like SDC (total reported: 5 cases) and low-grade intercalated-type intraductal carcinomas (4 cases). Given the therapeutic relevance of ALK fusions, inclusion of ALK IHC in any atypical-looking or androgen-poor SDC and in high-grade adenocarcinoma-not otherwise specified is recommended. Absence of aberrant ALK expression in genetically characterized secretory (n= 15) and intraductal (n= 9) carcinomas lacking ALK fusions underlines the value of ALK IHC as a diagnostic screening method for identifying potential cases.
CRIS-Team WoS Importer:2021-08-27

Analysis of CXCL9, PD1 and PD-L1 mRNA in stage T1 non-muscle invasive bladder cancer and their association with prognosis - Kubon, Jennifer; Sikic, Danijel; Eckstein, Markus; Weyerer, Veronika; Stöhr, Robert; Neumann, Angela; Keck, Bastian; Wullich, Bernd; Hartmann, Arndt; Wirtz, Ralph M.; Taubert, Helge; Wach, Sven (Cancers, 2020)
Non-muscle invasive bladder cancer (NMIBC), which is characterized by a recurrence rate of approximately 30% and very long treatment times, remains a major unresolved problem for patients and the health care system. The immunological interplay between tumor cells and the immune environment is important for tumor development. Therefore, we analyzed the mRNA of three immune markers, CXCL9, PD1 and PD-L1, in NMIBC by qRT-PCR. The results were subsequently correlated with clinicopathological parameters and prognostic data. Altogether, as expected, higher age was an independent prognostic factor for overall survival (OS) and disease-specific survival (DSS), but not for recurrence-free survival (RFS). Lower CXCL9 mRNA was observed in multivariate Cox’s regression analysis to be an independent prognostic parameter for reduced OS (relative risk; RR = 2.08; p = 0.049), DSS (RR = 4.49; p = 0.006) and RFS (RR = 2.69; p = 0.005). In addition, PD-L1 mRNA was an independent prognostic factor for DSS (RR = 5.02; p = 0.042) and RFS (RR = 2.07; p = 0.044). Moreover, in univariate Cox’s regression analysis, the stratification of patients revealed that low CXCL9 or low PD1 mRNA was associated with reduced RFS in the younger patient group (≤71 years), but not in the older patient group (>71 years). In addition, low CXCL9 or low PD-L1 was associated with shorter RFS in patients with higher tumor cell proliferation and in patients without instillation therapy. In conclusion, the characterization of mRNA levels of immune markers differentiates NIMBC patients with respect to prognosis.
CRIS-Team Scopus Importer:2020-10-09
Keywords: CXCL9; PD-L1; PD1; Prognosis; Stage T1 NMIBC

A Possible Distinct Molecular Subtype (Quintuple-Wildtype) of Metastatic Colorectal Cancer in First-Line Anti-EGFR Therapy with Cetuximab Plus FOLFIRI - Palliative Precision Therapy and a Multidisciplinary Treatment Approach: Interim Analysis of the IVOPAK II Trial with Early Results - Wein, Axel; Stöhr, Robert; Kersting, Stephan; Siebler, Jürgen; Merkel, Susanne; Busse, Daniel; Wolff, Kerstin; Ostermeier, Nicola; Neufert, Clemens; Vitali, Francesco; Eckstein, Markus; Roth, Jan-Peter; et al. (Oncology, 2021)
Objective: The study aimed to prospectively evaluate a new molecular biomarker panel (KRAS, NRAS, BRAF, PIK3CA, and ERBB2) for palliative first-line treatment of colorectal cancer (CRC), including a multidisciplinary treatment approach. The rate of secondary metastasis resections was assessed. Patients and Methods: A total of 40 patients with definitively nonresectable metastatic CRC were enrolled from 10 centers before the interim analysis (June 2019) of the IVOPAK II trial (Interdisciplinary Care with Quality Control in Palliative Treatment of Colorectal Cancer). After determination of 5 molecular biomarkers in the tumor (KRAS, exons 2-4; NRAS, exons 2-4; BRAF V600E; PIK3CA; and ERBB2), patients in the IVOPAK II study received FOLFIRI plus cetuximab for all-RAS/quintuple-wildtype disease and FOLFIRI plus bevacizumab in the case of RAS mutations. The current article presents the early description of the clinical outcome of the interim analysis of IVOPAK II comparing the all-RAS/quintuple-wildtype and RAS-mutations populations, including a multidisciplinary-treated case report of a quintuple-wildtype patient. Results: The quintuple-wildtype population treated with FOLFIRI plus cetuximab in first-line exhibited a significantly higher response rate and enhanced early tumor shrinkage in the interim analysis than the RAS-mutations population, as well as a high rate of secondary metastatic resections. Conclusion: Initial results of this new biomarker panel (quintuple-wildtype) are promising for anti-EGFR therapy with cetuximab plus doublet chemotherapy (FOLFIRI) in first-line treatment of metastatic CRC. These results warrant confirmation with higher case numbers in the IVOPAK II trial.
CRIS-Team WoS Importer:2021-11-05

Assessment of prognostic and predictive value of FGFR alterations (FGFRa) in a real-world cohort of patients (pts) with high-risk pT1 non-muscle-invasive bladder cancer (NMIBC) - Breyer, J.; Monga, M.; Mayr, R.; Otto, W.; Burger, M.; Eckstein, Markus; Stöhr, Robert; Erben, P.; Bolenz, C.; Eidt, S.; Sundaram, R.; Baig, M.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-10-30

Biomarker-stratified first-line treatment of right-sided metastatic colon cancer with interdisciplinary collaboration in the IVOPAK II trial - Vitali, Francesco; Merkel, Susanne; Schubart, Christoph; Schmid, Axel; Eckstein, Markus; Stöhr, Robert; Kersting, Stephan; Hartmann, Arndt; Grützmann, Robert; Wein, Axel (Anti-Cancer Drugs, 2024)
Patients with right-sided metastatic colon carcinoma have a significantly worse prognosis than those with left-sided colorectal cancer (CRC), regardless of treatment. The aim of the prospective IVOPAK II study was to implement an interdisciplinary guideline-conform personalized CRC palliative therapy of metastatic colorectal carcinoma and to improve the overall survival (OS) by multidisciplinary approach via secondary metastatic resection. We present the efficacy data of first-line treatment and the benefit of interdisciplinary collaboration of right-sided metastatic colon carcinoma patients: n = 25. RAS mutation: n = 20 (80%): received systemic first-line treatment: FOLFIRI plus bevacizumab. All-RAS-wildtype: n = 5 (20%): received systemic first-line treatment: FOLFIRI plus cetuximab. Last date evaluation: 31 January 2024. Median age: 59.6 years (range 42-71), men/women: 14/11. Eastern Cooperative Oncology Group (ECOG) index: 0/1/2 : 11/10/4. Evaluable for response: n = 25. Complete response: n = 0, partial response: n = 14 (56%), stable disease: n = 8 (32%), progressive disease: n = 3 (12%), early tumor shrinkage: n = 13 (52%), estimates progression-free survival: 13 months (95% CI 8-17 months), estimated OS: 48 months (95% CI 25-71 months), median follow-up: 26 months (1-61 months), no evidence of disease: n = 4 (16%). A chemotherapy doublette regimen with FOLFIRI plus a biological as first-line treatment shows promising efficacy and secondary metastatic resection after interdisciplinary discussion was associated with a survival benefit in right-sided metastatic colon carcinoma.
CRIS-Team Scopus Importer:2024-08-16
Keywords: biomarker guided first; line treatment; right; secondary metastatic resection; sided metastatic colon carcinoma

Bladder tumor subtype commitment occurs in carcinoma in-situ driven by key signaling pathways including ECM remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, J.; Burger, M.; et al. (EUROPEAN UROLOGY, 2021)
CRIS-Team WoS Importer:2021-08-20

Bladder Tumor Subtype Commitment Occurs in Carcinoma In Situ Driven by Key Signaling Pathways Including ECM Remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, Johannes; Burger, Maximilian; et al. (Cancer Research, 2021)
Basal and luminal subtypes of invasive bladder tumors have significant prognostic and predictive impacts for patients. However, it remains unclear whether tumor subtype commitment occurs in noninvasive urothelial lesions or in carcinoma in situ (CIS) and which gene pathways are important for bladder tumor progression. To understand the timing of this commitment, we used gene expression and protein analysis to create a global overview of 36 separate tissues excised from a whole bladder encompassing urothelium, noninvasive urothelial lesions, CIS, and invasive carcinomas. Additionally investigated were matched CIS, noninvasive urothelial lesions, and muscle-invasive bladder cancers (MIBC) from 22 patients. The final stage of subtype commitment to either a luminal or basal MIBC occurred at the CIS transition. For all tissues combined, hierarchical clustering of subtype gene expression revealed three subtypes: "luminal," "basal," and a "luminal p53-/extracellular matrix (ECM)-like" phenotype of ECM-related genes enriched in tumor-associated urothelium, noninvasive urothelial lesions, and CIS, but rarely invasive, carcinomas. A separate cohort of normal urothelium from noncancer patients showed significantly lower expression of ECM-related genes compared with tumor-associated urothelium, noninvasive urothelial lesions, and CIS. A PanCancer Progression Panel of 681 genes unveiled pathways specific for the luminal p53-/ECM-like cluster, for example, ECM remodeling, angiogenesis, epithelial-to-mesenchymal transition, cellular discohesion, cell motility involved in tumor progression, and cell proliferation and oncogenic ERBB2/ERBB3 signaling for invasive carcinomas. In conclusion, this study provides insights into bladder cancer subtype commitment and associated signaling pathways, which could help predict therapy response and enhance our understanding of therapy resistance.
CRIS-Team WoS Importer:2021-04-09

Case report: Immunovirotherapy as a novel add-on treatment in a patient with thoracic NUT carcinoma - Kloker, Linus D.; Calukovic, Branko; Benzler, Katrin; Golf, Alexander; Böhm, Sebastian; Günther, Sven; Horger, Marius; Haas, Simone; Berchtold, Susanne; Beil, Julia; Carter, Mary E.; Ganzenmueller, Tina; et al. (Frontiers in Oncology, 2022)
NUT carcinoma (NC) is a rare and extremely aggressive form of cancer, usually presenting with intrathoracic or neck manifestations in adolescents and young adults. With no established standard therapy regimen and a median overall survival of only 6.5 months, there is a huge need for innovative treatment options. As NC is genetically driven by a single aberrant fusion oncoprotein, it is generally characterized by a low tumor mutational burden, thus making it immunologically cold and insusceptible to conventional immunotherapy. Recently, we have demonstrated that oncolytic viruses (OVs) are able to specifically infect and lyse NC cells, thereby turning an immunologically cold tumor microenvironment into a hot one. Here, we report an intensive multimodal treatment approach employing for the first time an OV (talimogene laherparepvec (T-VEC); IMLYGIC®) together with the immune checkpoint inhibitor pembrolizumab as an add-on to a basic NC therapy (cytostatic chemotherapy, radiation therapy, epigenetic therapy) in a patient suffering from a large thoracic NC tumor which exhibits an aberrant, unique BRD3:NUTM1 fusion. This case demonstrates for the first time the feasibility of this innovative add-on immunovirotherapy regimen with a profound, repetitive and durable replication of T-VEC that is instrumental in achieving tumor stabilization and improvement in the patient´s quality of life. Further, a previously unknown BRD3:NUTM1 fusion gene was discovered that lacks the extraterminal domain of BRD3.
CRIS-Team Scopus Importer:2022-11-25
Keywords: BRD3; chemotherapy; immunotherapy; NUT carcinoma; NUTM1; T-VEC; virotherapy

CCL2 expression in tumor cells and tumor-infiltrating immune cells shows divergent prognostic potential for bladder cancer patients depending on lymph node stage - Eckstein, Markus; Epple, Elena; Jung, Rudolf; Weigelt, Katrin; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Kehlen, Astrid; Hartmann, Arndt; et al. (Cancers, 2020)
Bladder cancer (BCa) is the ninth most commonly diagnosed cancer worldwide. Although there are several well-established molecular and immunological classifications, markers for tumor cells and immune cells that are associated with prognosis are still needed. The chemokine CC motif ligand 2 (CCL2) could be such a marker. We analyzed the expression of CCL2 by immunohistochemistry (IHC) in 168 muscle invasive BCa samples using a tissue microarray. Application of a single cut-off for the staining status of tumor cells (TCs; positive vs. negative) and immune cells (ICs; ≤6% of ICs vs. >6% of ICs) revealed 57 cases (33.9%) and 70 cases (41.7%) with CCL2-positive TCs or ICs, respectively. IHC results were correlated with clinicopathological and survival data. Positive CCL2 staining in TCs was associated with shorter overall survival (OS), disease-specific survival (DSS), and relapse-free survival (RFS) (p = 0.004, p = 0.036, and p = 0.047; log rank test) and appeared to be an independent prognostic factor for OS (RR = 1.70; p = 0.007; multivariate Cox’s regression analysis). In contrast, positive CCL2 staining in the ICs was associated with longer OS, DSS, and RFS (p = 0.032, p = 0.001, and p = 0.001; log rank test) and appeared to be an independent prognostic factor for DSS (RR = 1.77; p = 0.031; multivariate Cox’s regression analysis). Most interestingly, after separating the patients according to their lymph node status (N0 vs. N1+2), CCL2 staining in the ICs was differentially associated with prognosis. In the N0 group, CCL2 positivity in the ICs was a positive independent prognostic factor for OS (RR = 1.99; p = 0.014), DSS (RR = 3.17; p = 0.002), and RFS (RR = 3.10; p = 0.002), whereas in the N1+2 group, CCL2 positivity was a negative independent factor for OS (RR = 3.44; p = 0.019)) and RFS (RR = 4.47; p = 0.010; all multivariate Cox’s regression analyses). In summary, CCL2 positivity in TCs is a negative prognostic factor for OS, and CCL2 can mark ICs that are differentially associated with prognosis depending on the nodal stage of BCa patients. Therefore, CCL2 staining of TCs and ICs is suggested as a prognostic biomarker for BCa patients.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Bladder cancer; CCL2; Immune cells; Lymph node stage; Prognosis; Tumor cells

Cell-Free DNA Sequencing Reveals Gene Variants in DNA Damage Repair Genes Associated with Prognosis of Prostate Cancer Patients - Lieb, Verena; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Bellut, Laura; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2022)
In the present study, we further analyzed the data obtained in our previous study, where we investigated the cell-free DNA (cfDNA) of 34 progressive prostate cancer patients via targeted sequencing. Here, we studied the occurrence and prognostic impact of sequence variants according to their clinical pathological significance (CPS) or their functional impact (FI) in 23 DNA damage repair (DDR) genes with a focus on the ATM serine/threonine kinase gene (ATM). All patients had at least one DDR gene with a CPS or FI variant. Kaplan-Meier analysis indicated that the group with a higher number of CPS variants in DDR genes had a shorter time to treatment change (TTC) compared to the group with a lower number of CPS variants (p = 0.038). Analysis of each DDR gene revealed that CPS variants in the ATM gene and FI variants in the nibrin (NBN) gene showed a shorter TTC (p = 0.034 and p = 0.042). In addition, patients with CPS variants in the ATM gene had shorter overall survival (OS; p = 0.022) and disease-specific survival (DSS; p = 0.010) than patients without these variants. Interestingly, patients with CPS variants in seven DDR genes possessed a better OS (p = 0.008) and DSS (p = 0.009), and patients with FI variants in four DDR genes showed a better OS (p = 0.007) and DSS (p = 0.008). Together, these findings demonstrated that the analysis of cfDNA for gene variants in DDR genes provides prognostic information that may be helpful for future temporal and targeted treatment decisions for advanced PCa patients.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ATM; cfDNA; DDR genes; NBN; prognosis; prostate cancer; sequence variants

Cell-free dna variant sequencing using plasma and ar-v7 testing of circulating tumor cells in prostate cancer patients - Lieb, Verena; Bellut, Laura; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2021)
Prostate cancer (PCa) is the second most common malignant cancer and is a major cause of morbidity and mortality among men worldwide. There is still an urgent need for biomarkers applicable for diagnosis, prognosis, therapy prediction, or therapy monitoring in PCa. Liquid biopsies, including cell-free DNA (cfDNA) and circulating tumor cells (CTCs), are a valuable source for studying such biomarkers and are minimally invasive. In our study, we investigated the cfDNA of 34 progressive PCa patients, via targeted sequencing, for sequence variants and for the occurrence of CTCs, with a focus on androgen receptor splice variant 7 (AR-V7)-positive CTCs. The cfDNA content was associated with overall survival (OS; p = 0.014), disease-specific survival (DSS; p = 0.004), and time to treatment change (TTC; p = 0.001). Moreover, when considering all sequence variants grouped by their functional impact and allele frequency, a significant association with TTC (p = 0.017) was observed. When investigating only pathogenic or likely pathogenic gene variants, variants of the BRCA1 gene (p = 0.029) and the AR ligand-binding domain (p = 0.050) were associated with a shorter TTC. Likewise, the presence of CTCs was associated with a shorter TTC (p = 0.031). The presence of AR-V7-positive CTCs was associated with TTC (p < 0.001) in Kaplan–Meier analysis. Interestingly, all patients with AR-V7-positive CTCs also carried TP53 point mutations. Altogether, analysis of cfDNA and CTCs can provide complementary information that may support temporal and targeted treatment decisions and may elucidate the optimal choice within the variety of therapy options for advanced PCa patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: CfDNA; CTCs; Prognosis; prostate cancer; Sequence variants

Clinicopathological, immunohistochemical, molecular-genetic and risk profiles of gastrointestinal stromal tumors in a cohort of Sudanese patients - Husain, Nazik Elmalaika; Osman, Ihsan Mohamed; Khalid, Ahmed; Satir, Ali Abdel; Stöhr, Robert; Agaimy, Abbas (African Health Sciences, 2023)
Background: Determining the risk of malignant behaviour and mutational status of gastrointestinal stromal tumours (GISTs) guide the management decision and allow optimal individualized patient treatment.Objectives: To determine clinicopathological, immunohistochemical (IHC), risk and KIT mutational findings of GISTs in Sudanese patients. Methods: Histological slides were reviewed, IHC for DOG-1 and CD117 performed and hotspot KIT mutations examined. The risk group was assigned using combined risk criteria.Results: 21 of the 36 patients (58.3%) were males (mean age, 54.83 +/- 12.57; range, 26-71). Abdominal pain and mass were the most frequent symptoms. Mean tumor size (+/- SD) was 11.6(+/- 5.82) cm. Either CD117, DOG1 or both were positive in all cases. Using risk criteria, 33.3% (n=12) were clinically malignant at presentation, 13.9% (n=5) high risk, 16.7% (n=6) intermediate, 27.8% (n=10) low risk and 2.8% (n=1) very low risk. Sixteen of 23 (70%) tested cases had KIT (14 exon 11 and two exon 9) mutations. Six tumors were wild type. Exon 11 deletions (p.I563-L576 del and p.V559-N566delinsD) significantly correlate with disease recurrence (p-value: 0.028). Conclusions: Sudanese patients with GIST tend to present late. Nearly half of them correspond to the malignant/high-risk category. The frequency of KIT mutations (79.31%) is in line with the literature.
CRIS-Team WoS Importer:2023-06-02
Keywords: Gastrointestinal stromal tumour; GIST; risk stratification; malignant behaviour; risk assessment; tumour rupture; metastasis; Imatinib; genotyping; KIT; DOG1

Combination of GP88 Expression in Tumor Cells and Tumor-Infiltrating Immune Cells Is an Independent Prognostic Factor for Bladder Cancer Patients - Eckstein, Markus; Lieb, Verena; Jung, Rudolf; Sikic, Danijel; Weigelt, Katrin; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Serrero, Ginette; Yue, Binbin; Hartmann, Arndt; et al. (Cells, 2021)
Urothelial bladder cancer (BCa) is the ninth most commonly diagnosed cancer worldwide and accounts for approximately 3% of global cancer diagnoses. We are interested in prognostic markers that may characterize tumor cells (TCs) and immune cells (ICs) and their relationship in BCa. A potential candidate marker that meets these criteria is progranulin (GP88), which is expressed separately in TCs and ICs. We analyzed GP88 expression by immunohistochemistry (IHC) in 196 muscle-invasive BCa samples using a tissue microarray. The immunoreactive score for GP88 staining in TCs and the percentage of GP88-positive ICs was determined. An easy cutoff for the staining status of TCs (positive vs. negative) and ICs (0% vs. >0%) and, more generally, negative vs. positive GP88 staining could be applied. We detected 93 patients (47.4%) and 92 patients (46.9%) with GP88-positive TCs or ICs, respectively. The IHC results were correlated with clinicopathological and survival data. Positive GP88 staining in TCs appeared to be an independent poor prognostic factor for disease-specific survival (DSS) (RR (relative risk) = 1.74; p = 0.009) and recurrence-free survival (RFS) (RR = 1.92; p = 0.002). In contrast, negative GP88 staining in ICs was an independent negative predictor for overall survival (OS) (RR = 2.18; p < 0.001), DSS (RR = 2.84; p < 0.001) and RFS (RR = 2.91; p < 0.001) in multivariate Cox's regression analysis. When combining GP88 staining in TCs and ICs, a specific combination of GP88-positive TCs and GP88-negative ICs was associated with a 2.54-fold increased risk of death, a 4.21-fold increased risk of disease-specific death and a 4.81-fold increased risk of recurrence compared to GP88-negative TCs and GP88-positive ICs. In summary, GP88 positivity in TCs is a negative prognostic factor for DSS and RFS. In addition, GP88 positivity can mark ICs that are associated with a good prognosis (OS, DSS and RFS). The combination of GP88 staining in TCs and ICs appears to be a significant independent prognostic biomarker in muscle-invasive BCa.
CRIS-Team WoS Importer:2021-08-06

Combined miR-486 and GP88 (Progranulin) Serum Levels Are Suggested as Supportive Biomarkers for Therapy Decision in Elderly Prostate Cancer Patients - Fichte, Alexander; Neumann, Anna-Dorothea; Weigelt, Katrin; Guzman, Juan; Jansen, Thilo; Keinert, Julia; Serrero, Ginette; Yue, Binbin; Stöhr, Robert; Greither, Thomas; Hartmann, Arndt; Wullich, Bernd; et al. (Life, 2022)
Our study aimed to assess the applicability of miR-486 in combination with soluble GP88 protein as a diagnostic and/or predictive biomarker for prostate cancer (PCa) patients. miR-486 and GP88 levels in serum samples from 136 patients undergoing MRI-guided biopsy of the prostate were assessed by qRT–PCR and ELISA, respectively. Of these, 86 patients received a histologically confirmed diagnosis of PCa. Neither marker showed an association with the diagnosis of cancer. PCa patients were separated based on (i) treatment into patients with active surveillance or patients with any type of curative treatment and (ii) age into elderly (>68 years) patients and younger patients (≤68 years). In elderly patients (N = 41) with the intention of curative treatment at optimized cut-off values, significantly higher GP88 levels (p = 0.018) and lower miR-486 levels (p = 0.014) were observed. The total PSA level and ISUP biopsy grade were used in a baseline model for predicting definitive therapy. The baseline model exhibited an area under the curve (AUC) of 0.783 (p = 0.005). The addition of the serum biomarkers miR-486 and GP88 to the baseline model yielded an improved model with an AUC of 0.808 (p = 0.002). Altogether, combined miR-486 and GP88 serum levels are associated with and are therefore suggested as supportive biomarkers for therapy decisions, particularly in elderly PCa patients.
CRIS-Team Scopus Importer:2022-06-03
Keywords: age; miRNAs; predictive biomarker; progranulin; prostate cancer; serum level

Comparative analysis of tumour mutational burden (TMB) prediction methods and its association with determinants of the tumour immune microenvironment of urothelial bladder cancer (UBC) - Eckstein, Markus; Hartmann, Arndt; Strissel, Pamela; Strick, Reiner; Wach, S.; Taubert, Helge; Wullich, Bernd; Geppert, Carol-Immanuel; Weyerer, Veronika; Stöhr, Robert; Rübner, Matthias; Fasching, Peter; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Comparative genomic profiling of glandular bladder tumours - Maurer, Angela; Ortiz-Bruechle, Nadina; Guricova, Karolina; Rose, Michael; Morsch, Ronja; Garczyk, Stefan; Stöhr, Robert; Bertz, Simone; Golz, Reinhard; Reis, Henning; Bremmer, Felix; Zimpfer, Annette; et al. (Virchows Archiv, 2020)
Primary glandular bladder tumours (bladder adenocarcinoma [BAC], urachal adenocarcinoma [UAC], urothelial carcinoma with glandular differentiation [UCg]) are rare malignancies with histological resemblance to colorectal adenocarcinoma (CORAD) in the majority of this subgroup. Definite case numbers are very low, molecular data are limited and the pathogenesis remains poorly understood. Therefore, this study was designed to complement current knowledge by in depth analysis of BAC (n = 12), UAC (n = 13), UCg (n = 11) and non-invasive glandular lesions (n = 19). In BAC, in addition to known alterations in TP53, Wnt, MAP kinase and MTOR pathway, mutations in SMAD4, ARID1A and BRAF were identified. Compared to published data on muscle invasive bladder cancer (BLCA) and CORAD, UCg exhibited frequent "urothelial" like alterations while BAC and UAC were characterised by a more "colorectal" like mutational pattern. Immunohistochemically, there was no evidence of DNA mismatch repair deficiency or PD-L1 tumour cell positivity in any sample. Depending on the used antibody 0-45% of BAC, 0-30% of UCg and 0% UAC cases exhibited PD-L1 expressing tumour associated immune cells. A single BAC (9%, 1/11) showed evidence of ARID1A protein loss, and two cases of UCg (20%, 2/10) showed loss of SMARCA1 and PBRM1, respectively. Taken together, our data suggest at least in part involvement of similar pathways driving tumourigenesis of adenocarcinomas like BAC, UAC and CORAD independent of their tissue origin. Alterations of TERT and FBXW7 in single cases of intestinal metaplasia further point towards a possible precancerous character in line with previous reports.
CRIS-Team WoS Importer:2020-04-07

Correction to: Multicenter evaluation of an automated, multiplex, RNA-based molecular assay for detection of ALK, ROS1, RET fusions and MET exon 14 skipping in NSCLC (Virchows Archiv, (2024), 10.1007/s00428-024-03778-9) - Melchior, Linea; Hirschmann, Astrid; Hofman, Paul; Bontoux, Christophe; Concha, Angel; Mrabet‑Dahbi, Salima; Vannuffel, Pascal; Watkin, Emmanuel; Putzová, Martina; Scarpino, Stefania; Cayre, Anne; Martin, Paloma; et al. (Virchows Archiv, 2024)
In the original version of this article, the given and family names of the authors were interchanged. The names were displayed correctly in all versions at the time of publication. The original article has been corrected.
CRIS-Team Scopus Importer:2024-05-17

Cytotoxic T-cell-related gene expression signature predicts improved survival in muscle-invasive urothelial bladder cancer patients after radical cystectomy and adjuvant chemotherapy - Eckstein, Markus; Strissel, Pamela; Strick, Reiner; Weyerer, Veronika; Wirtz, Ralph; Pfannstiel, Carolin; Wullweber, Adrian; Lange, Fabienne; Erben, Philipp; Stöhr, Robert; Bertz, Simone; Geppert, Carol-Immanuel; et al. (Journal for ImmunoTherapy of Cancer, 2020)
Background Assessment of the immune status of muscle-invasive bladder cancer (MIBC) has previously shown to be prognostically relevant after treatment with curative intent. We conducted this study to develop a clinically applicable immune gene expression assay to predict prognosis and adjuvant chemotherapy benefit. Patients and methods Gene expression of CD3Z, CD8A and CXCL9, immune cell (IC) populations including stromal tumor infiltrating lymphocytes (sTILs), T-cells, natural killer cells (NK-cells), macrophages, Programmed cell death protein 1 positive (PD-1) IC and tumor subtypes (MD Anderson Cancer Center/MDACC-approach) were assessed in 187 MIBC patients (Comprehensive Cancer Center Erlangen-EMN/CCC-EMN-cohort). A gene expression signature was derived by hierarchical-clustering and validated in The Cancer Genome Atlas (TCGA)-cohort. IC populations in the TCGA cohort were assessed via CIBERSORT. Benefit of platinum-containing adjuvant chemotherapy was assessed in a pooled cohort of 125 patients. Outcome measurements were disease specific survival, disease-free survival and overall survival. Results The gene expression signature of CXCL9, CD3Z and CD8A correlates with quantitative amounts of specific IC populations and sTILs (CCC-EMN: ρ-range: 0.44-0.74; TCGA: ρ-range: 0.56-0.82) and allows stratification of three different inflammation levels (inflamed high, inflamed low, uninflamed). Highly inflamed tumors are preferentially basal subtype and show favorable 5-year survival rates of 67.3% (HR=0.27; CCC-EMN) and 55% (HR=0.41; TCGA). Uninflamed tumors are predominantly luminal subtypes and show low 5-year survival rates of 28% (CCC-EMN) and 36% (TCGA). Inflamed tumors exhibit higher levels of PD-1 and Programmed cell death 1 ligand 1 (PD-L1). Patients undergoing adjuvant platinum-based chemotherapy with 'inflamed high' tumors showed a favorable 5-year survival rate of 64% (HR=0.27; merged CCC-EMN and TCGA cohort). Conclusion The gene expression signature of CD3Z, CD8A and CXCL9 can assess the immune status of MIBC and stratify the survival of MIBC patients undergoing surgery and adjuvant platinum-based chemotherapy. Furthermore, the assay can identify patients with immunological hot tumors with particular high expression of PD-L1 potentially suitable for immunotherapy.
CRIS-Team Scopus Importer:2020-06-05
Keywords: immunology; pathology; urology

Dedifferentiated and Undifferentiated Melanomas: Report of 35 New Cases with Literature Review and Proposal of Diagnostic Criteria - Agaimy, Abbas; Stöhr, Robert; Hornung, Annkathrin; Popp, Judith; Erdmann, Michael; Heinzerling, Lucie; Hartmann, Arndt (American Journal of Surgical Pathology, 2021)
Dedifferentiated melanoma (DM) and undifferentiated melanoma (UM) is defined as a primary or metastatic melanoma showing transition between conventional and undifferentiated components (DM) or lacking histologic and immunophenotypic features of melanoma altogether (UM). The latter is impossible to verify as melanoma by conventional diagnostic tools alone. We herein describe our experience with 35 unpublished cases to expand on their morphologic, phenotypic, and genotypic spectrum, along with a review of 50 previously reported cases (total: 85) to establish the diagnostic criteria. By definition, the dedifferentiated/undifferentiated component lacked expression of 5 routinely used melanoma markers (S100, SOX10, Melan-A, HMB45, Pan-melanoma). Initial diagnoses (known in 66 cases) were undifferentiated/unclassified pleomorphic sarcoma (n=30), unclassified epithelioid malignancy (n=7), pleomorphic rhabdomyosarcoma (n=5), other specific sarcoma types (n=6), poorly differentiated carcinoma (n=2), collision tumor (n=2), atypical fibroxanthoma (n=2), and reactive osteochondromatous lesion (n=1). In only 11 cases (16.6%) was a diagnosis of melanoma considered. Three main categories were identified: The largest group (n=56) comprised patients with a history of verified previous melanoma who presented with metastatic DM or UM. Axillary or inguinal lymph nodes, soft tissue, bone, and lung were mainly affected. A melanoma-compatible mutation was detected in 35 of 48 (73%) evaluable cases: BRAF (n=20; 40.8%), and NRAS (n=15; 30.6%). The second group (n=15) had clinicopathologic features similar to group 1, but a melanoma history was lacking. Axillary lymph nodes (n=6) was the major site in this group followed by the lung, soft tissue, and multiple site involvement. For this group, NRAS mutation was much more frequent (n=9; 60%) than BRAF (n=3; 20%) and NF1 (n=1; 6.6%). The third category (n=14) comprised primary DM (12) or UM (2). A melanoma-compatible mutation was detected in only 7 cases: BRAF (n=2), NF1 (n=2), NRAS (n=2), and KIT exon 11 (n=1). This extended follow-up study highlights the high phenotypic plasticity of DM/UM and indicates significant underrecognition of this aggressive disease among general surgical pathologists. The major clues to the diagnosis of DM and UM are: (1) presence of minimal differentiated clone in DM, (2) earlier history of melanoma, (3) undifferentiated histology that does not fit any defined entity, (4) locations at sites that are unusual for undifferentiated/unclassified pleomorphic sarcoma (axilla, inguinal, neck, digestive system, etc.), (5) unusual multifocal disease typical of melanoma spread, (6) detection of a melanoma-compatible gene mutation, and (7) absence of another genuine primary (eg, anaplastic carcinoma) in other organs.
CRIS-Team Scopus Importer:2021-02-05
Keywords: BRAF; chondrosarcoma; dedifferentiated melanoma; giant cell tumor; KIT; NRAS; osteosarcoma; pleomorphic sarcoma; rhabdomyosarcoma; undifferentiated melanoma

DEK-AFF2 Carcinoma of the Sinonasal Region and Skull Base Detailed Clinicopathologic Characterization of a Distinctive Entity - Rooper, Lisa M.; Agaimy, Abbas; Dickson, Brendan C.; Dueber, Julie C.; Eberhart, Charles G.; Gagan, Jeffrey; Hartmann, Arndt; Khararjian, Armen; London, Nyall R.; Macmillan, Christina M.; Palsgrove, Doreen N.; Nix, J. Stephen; et al. (American Journal of Surgical Pathology, 2021)
A novel DEK-AFF2 fusion was recently reported in 4 nonkeratinizing squamous cell carcinomas of the sinonasal region and skull base, including 1 with exceptional response to immunotherapy, but it is not yet clear if this rearrangement defines a unique clinicopathologic category or represents a rare event. This study aims to characterize a larger cohort of carcinomas with DEK-AFF2 fusions to assess whether they truly constitute a distinctive entity. Among 27 sinonasal and skull base nonkeratinizing squamous cell carcinoma that were negative for human papillomavirus and Epstein-Barr virus, RNA sequencing identified DEK-AFF2 fusions in 13 cases (48%). Nine were centered in the nasal cavity, 2 in the middle ear/temporal bone, 1 in the nasopharynx, and 1 in the orbit. These tumors displayed recurrent histologic features including (1) complex endophytic and exophytic, frequently papilloma-like growth, (2) transitional epithelium with eosinophilic to amphophilic cytoplasm, (3) absent or minimal keratinization with occasional compact keratin pearls, (4) monotonous nuclei, and (5) prominent tumor-infiltrating neutrophils or stromal lymphocytes. This appearance not only overlaps with high-grade basaloid sinonasal carcinomas but also with benign papillomas and tumors reported as low-grade papillary Schneiderian carcinoma. However, DEK-AFF2 carcinomas showed frequent local recurrence, cervical lymph node metastases, and distant metastasis with 2 deaths from disease, confirming they are aggressive malignancies despite relatively bland histology. Overall, the distinctive molecular, histologic, and clinical features of DEK-AFF2 carcinomas suggest they represent a unique entity in the sinonasal region. This tumor merits increased pathologic recognition to better understand its prognostic and therapeutic implications.
CRIS-Team WoS Importer:2021-11-26

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

Diagnostic and Prognostic Implications of FGFR3high/Ki67high Papillary Bladder Cancers - Geelvink, Mirja; Babmorad, Armin; Maurer, Angela; Stöhr, Robert; Grimm, Tobias; Bach, Christian; Knuechel, Ruth; Rose, Michael; Gaisa, Nadine T. (International Journal of Molecular Sciences, 2018)
Prognostic/therapeutic stratification of papillary urothelial cancers is solely based upon histology, despite activated FGFR3-signaling was found to be associated with low grade tumors and favorable outcome. However, there are FGFR3-overexpressing tumors showing high proliferation-a paradox of coexisting favorable and adverse features. Therefore, our study aimed to decipher the relevance of FGFR3-overexpression/proliferation for histopathological grading and risk stratification. N = 142 (n = 82 pTa, n = 42 pT1, n = 18 pT2-4) morphologically G1⁻G3 tumors were analyzed for immunohistochemical expression of FGFR3 and Ki67. Mutation analysis of FGFR3 and TP53 and FISH for FGFR3 amplification and rearrangement was performed. SPSS 23.0 was used for statistical analysis. Overall FGFR3high/Ki67high status (n = 58) resulted in a reduced ∆mean progression-free survival (PFS) (p < 0.01) of 63.92 months, and shorter progression-free survival (p < 0.01; mean PFS: 55.89 months) in pTa tumors (n = 50). FGFR3mut/TP53mut double mutations led to a reduced ∆mean PFS (p < 0.01) of 80.30 months in all tumors, and FGFR3mut/TP53mut pTa tumors presented a dramatically reduced PFS (p < 0.001; mean PFS: 5.00 months). Our results identified FGFR3high/Ki67high papillary pTa tumors as a subgroup with poor prognosis and encourage histological grading as high grade tumors. Tumor grading should possibly be augmented by immunohistochemical stainings and suitable clinical surveillance by endoscopy should be performed.
EVALuna2:205512

DICER1-Mutated Botryoid Fibroepithelial Polyp of the Parotid Duct: Report of the First Case - Erber, Ramona; Preidl, Raimund; Stöhr, Robert; Haller, Florian; Hartmann, Arndt; Kesting, Marco Rainer; Agaimy, Abbas (Head and Neck Pathology, 2021)
DICER1, a member of the ribonuclease III family, is involved in the biogenesis of microRNAs and, hence, it influences gene expression regulation. DICER1 germline (associated with the inherited DICER1 syndrome) or somatic mutations have been linked to tumorigenesis in histogenetically diverse benign and malignant neoplasms in different organs including pleuropulmonary blastoma, cystic nephroma, embryonal rhabdomyosarcoma, nasal chondromesenchymal hamartoma, poorly differentiated thyroid carcinoma, thyroblastoma, intracranial sarcoma and gonadal Sertoli-Leydig cell tumors in addition to others. Moreover, rare botryoid (giant) fibroepithelial polyps may harbor this mutation. Herein, we describe the first reported case of a DICER1-mutated botryoid fibroepithelial polyp occurring within the parotid duct of a 65-year-old female who has no other features or family history of the DICER1 syndrome. Based on its distinctive morphology, we tested this lesion specifically for DICER1 mutations and confirmed the presence of a pathogenic DICER1 variant with a low allele frequency, consistent with a somatic mutation.
CRIS-Team WoS Importer:2021-07-30

Digital volumetric assessment of CIS and tumor mass compliments conventional histopathological assessment in muscle-invasive urothelial bladder cancer - Lange, Fabienne; Geppert, Carol-Immanuel; Bahlinger, Veronika; Bertz, Simone; Stöhr, Robert; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (Virchows Archiv, 2024)
Carcinoma in situ (CIS) of the bladder is a known parameter regarding the prognosis and recurrence tendency of urothelial carcinomas. Nevertheless, there is little evidence whether the amount of CIS or other precursor lesions, as well as the quantified tumor mass of muscle-invasive urothelial carcinoma, has an influence on the survival or recurrence rate of affected patients. From 80 patients with muscle invasive urothelial bladder cancer and radical cystectomy, 23 samples each were obtained as part of a whole organ mapping in a single institution study, in which the precursor lesions and tumor area were digitally measured and further correlated to pathological standard parameters, patient survival, molecular luminal and basal subtypes, and immune infiltration. Significant correlations were found between tumor mass and surface lining CIS amount for pT-stage, lymphovascular invasion, and perineural infiltration. Furthermore, an increased tumor mass as well as an increased amount of CIS combined with an increased tumor mass showed a significantly reduced survival rate in multivariable analysis (HR = 2.75; P = 0.019 vs. HR = 3.54; P = 0.002) as well as a significantly increased recurrence. No correlations could be found with molecular subtypes and immune infiltration. The exact measurement of the tumor mass with and without the CIS surface area, whether manually or, more specifically, digitally, could be incorporated into routine diagnostics and implemented as an independent predictor for patient post-surgical outcomes. It can therefore serve as an additional predictor for risk stratification and, if necessary, intensified follow-up care or therapy.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Muscle invasive bladder cancer; Prognosis; Radical cystectomy; Survival; Urothelial carcinoma; Urothelial carcinoma in situ

Distinct genetic alterations and luminal molecular subtype in nested variant of urothelial carcinoma - Weyerer, Veronika; Weisser, Rebecca; Moskalev, Evgeny; Haller, Florian; Stöhr, Robert; Eckstein, Markus; Zinnall, Ulrike; Gaisa, Nadine T.; Comperat, Eva; Perren, Aurel; Keck, Bastian; Allory, Yves; et al. (Histopathology, 2019)
Aims Nested variant of urothelial carcinoma (NVUC) is rare, and only a few small series exist. Molecular characteristics and the classifying marker profile as well as therapeutic targets of this specific variant are mostly unknown. The aim of this study was to characterise NVUC at the molecular level in one of the largest cohorts to date. In addition, we applied an immunohistochemical marker panel in order to define the molecular subtype. Methods and results Sixty NVUC cases were collected from different departments. TERT promoter mutation analysis was carried out in all samples using SNaPshot analysis. Targeted sequencing of 48 cancer-related genes by next-generation sequencing (NGS) analysis was performed in a subset of 26 cases. Immunohistochemical markers CD44, CK5, CK14, EGFR, p63, FOXA1, GATA3, CD24 and CK20 were used to elucidate the molecular subtype. A total of 62.5% of NVUC cases harboured a mutation of the TERT promoter. Additionally, TP53, JAK3 and CTNNB1 were among the most frequently mutated genes identified by NGS analysis. Subtyping revealed that all NVUC express luminal markers such as CD24, FOXA1, GATA3 and CK20. Conclusions In summary, NVUC belong to the luminal molecular subtype. Moreover, a subset of NVUC seems to be characterised by mutations of the Wnt and inflammatory pathways, including JAK3 mutations, indicating a different biological background compared to conventional urothelial bladder cancer.
CRIS-Team WoS Importer:2019-11-01

Efficacy of anti-PD(L)1 treatment in patients with metastatic urothelial cancer based on mRNA- and protein- based PD-L1 determination: Results from the multicentric, retrospective FOsMIC trial - Jarczyk, J.; Wirtz, R.; Roghmann, F.; Juette, H.; Kriegmair, M. C.; Worst, T. S.; Sikic, D.; Wach, S.; Taubert, Helge; Wullich, Bernd; Weyerer, Veronika; Stöhr, Robert; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Elevated Microsatellite Alterations at Selected Tetranucleotide Repeats (EMAST) in Penile Squamous Cell Carcinoma-No Evidence for a Role in Carcinogenesis. - Fiegl, August; Wendler, Olaf; Giedl, Josef; Gaisa, Nadine T.; Richter, Georg; Campean, Valentina; Burger, Maximilian; Simmer, Femke; Nagtegaal, Iris; Wullich, Bernd; Bertz, Simone; Hartmann, Arndt; et al. (Current Oncology, 2024)
Penile squamous cell carcinoma (pSCC) is a rare malignancy with a global incidence ranging from 0.1 to 0.7 per 100,000 males. Prognosis is generally favorable for localized tumors, but metastatic pSCC remains challenging, with low survival rates. The role of novel biomarkers, such as tumor mutational burden (TMB) and microsatellite instability (MSI), in predicting the response to immune checkpoint inhibitors (ICIs) has been investigated in various cancers. However, MSI has not been observed in pSCC, limiting immunotherapy options for this patient subgroup. Elevated microsatellite alterations at selected tetranucleotide repeats (EMAST) are a distinct form of genomic instability associated with deficient MSH3 expression, which has been proposed as a potential biomarker in several cancers. This study investigates EMAST and MSH3 expression in a cohort of 78 pSCC cases using PCR, fragment analysis and immunohistochemistry. For the detection of EMAST, the stability of five microsatellite markers (D9S242, D20S82, MYCL1, D8S321 and D20S85) was analyzed. None of the cases showed an instability. As for MSH3 immunohistochemistry, all analyzable cases showed retained MSH3 expression. These results strongly suggest that neither EMAST nor MSH3 deficiency is involved in the carcinogenesis of pSCC and do not represent reliable predictive biomarkers in this entity. Furthermore, these findings are in full agreement with our previous study showing a very low frequency of MSI and further support the thesis that EMAST and MSI are strongly interconnected forms of genomic instability. Further research is needed to explore novel therapeutic targets and predictive biomarkers for immunotherapy in this patient population.
EVALuna2:578801

Eosinophilic cystitis mimicking bladder cancer—considerations on the management based upon a case report and a review of the literature - Schmitz-Draeger, Bernd J.; Skutetzki, Andreas; Rieker, Ralf J.; Schwab, Siegfried A.; Stöhr, Robert; Bismarck, Ekkehardt; Savov, Orlin; Ebert, Thomas; Benderska-Soeder, Natalya; Hartmann, Arndt (Virchows Archiv, 2021)
The hypereosinophilic syndrome (HES) is a rare disorder characterized by hypereosinophilia and infiltration of various organs with eosinophils. Eosinophilic cystitis (EC), mimicking bladder cancer clinically but also in ultrasound and in radiographic imaging, is one potential manifestation of the HES occurring in adults as well as in children. This case report describes the course of disease in a 57-year-old male presenting with severe gait disorders and symptoms of a low compliance bladder caused by a large retropubic tumor. After extensive urine and serologic examination and histologic confirmation of EC the patient was subjected to medical treatment with cetirizine and prednisolone for 5 weeks. While gait disorders rapidly resolved, micturition normalized only 10 months after initiation of therapy. Based upon this course the authors recommend patience and reluctance concerning radical surgical intervention in EC.• Genetic alterations (e.g., BRAF mutations) may predispose for the disease
CRIS-Team Scopus Importer:2021-03-05
Keywords: Bladder tumor; Eosinophilic cystitis; Hypereosinophilic syndrome; Inflammatory pseudotumor

ERBB2/ ERBB3-mutated S100/ SOX10-positive unclassified high-grade uterine sarcoma: first detailed description of a novel entity - Agaimy, Abbas; Dermawan, Josephine K.; Haller, Florian; Semrau, Sabine; Meidenbauer, Norbert; Stöhr, Robert; Lax, Sigurd; Hartmann, Arndt; Zou, Ying S.; Xing, Deyin; Tögel, Lars; Gross, John M.; et al. (Virchows Archiv, 2024)
With the increasing use of innovative next generation sequencing (NGS) platforms in routine diagnostic and research settings, the genetic landscape of uterine sarcomas has been dynamically evolving during the last two decades. Notably, the majority of recently recognized genotypes in uterine sarcomas represent gene fusions, while recurrent oncogene mutations of diagnostic and/ or therapeutic value have been rare. Recently, a distinctive aggressive uterine sarcoma expressing S100 and SOX10, but otherwise lacking diagnostic morphological, immunophenotypic and molecular features of other uterine malignancies has been presented in a scientific abstract form (USCAP, 2023), but detailed description and delineation of the entity is still missing. We herein describe two high-grade unclassified uterine sarcomas characterized by spindle to round cell morphology and diffuse expression of S100 and SOX10, originating in the uterine body and cervix of 53- and 45-year-old women and carrying an ERBB3 (p.Glu928Gly) and an ERBB2 (p.Val777Leu) mutation, respectively. Both tumors harbored in addition genomic HER2 amplification, ATRX mutation and CDKN2A deletion. Methylation studies revealed a methylome most similar to MPNST-like tumors, but distinct from melanoma, MPNST, clear cell sarcoma, and endometrial stromal sarcoma. Case 1 died of progressive peritoneal metastases after multiple trials of chemotherapy 47 months after diagnosis. Case 2 is a recent case who presented with a cervical mass, which was biopsied. This study defines a novel heretofore unrecognized aggressive uterine sarcoma with unique phenotypic and genotypic features. Given the potential value of targeting HER2, recognizing this tumor type is mandatory for appropriate therapeutic strategies and for better future delineation of the entity.
CRIS-Team Scopus Importer:2024-09-06
Keywords: EGFR; Molecular profiling; nerve sheath tumor; Targeted therapy; Tyrosine kinase fusions; Undifferentiated uterine sarcoma

Europe-side external quality assessment (EQA) of RNA based testing of ER, PR, HER2 and Ki67 in invasive breast cancer - Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Stöhr, Robert; Beckmann, Matthias; Zentgraf, M.; Rübner, Matthias; Hübner, Hanna; Fischer, J.; Guerini Rocco, E.; Viale, G.; Cayre, A.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-06-26

Evaluation of different diagnostic methods for identification of FGFR alteration in advanced urothelial carcinomas: Proficiency results based on multiple RNA extraction kits and mutation detection methods - Weyerer, Veronika; Stöhr, Robert; Juette, H.; Wirtz, R.; Eckstein, Markus; Roghmann, F.; Breyer, J.; Porubsky, S.; Sikic, D.; Bolenz, C.; Kriegmair, M. C.; Hartmann, Arndt; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Evaluation of FGFR Alteration Status in Urothelial Tumors - Bahlinger, Veronika; Eckstein, Markus; Hartmann, Arndt; Stöhr, Robert (Urothelial Carcinoma - Methods and Protocols, 2023)
FGFR alterations in urothelial carcinoma are key driver alterations of tumorigenesis and are long recognized. In 2019 the Food and Drug Administration (FDA) approved the first pan-FGFR inhibitor, as the first specific targeted therapy in urothelial carcinoma. To receive the drug, alteration testing is required, and only alteration carriers can profit of this new agent. Due to this clinical need of detection and analysis of FGFR, here we describe two distinct and specific analytical methodologies: the SNaPshot analysis of nine FGFR3 point mutations and the QIAGEN therascreen® FGFR RGQ RT-PCR Kit, the FDA-approved companion diagnostic kit.
CRIS-Team Scopus Importer:2023-07-21
Keywords: FGFR testing; Inhibitor; QIAGEN therascreen; SNaPshot analysis; Targeted therapy; Urothelial carcinoma

EWSR1::ATF1 fusions characterize a group of extra-abdominal epithelioid and round cell mesenchymal neoplasms, phenotypically overlapping with sclerosing epithelioid fibrosarcomas, and intra-abdominal FET::CREB fusion neoplasms - Rekhi, Bharat; Dermawan, Josephine K.; Fritchie, Karen J.; Zimpfer, Annette; Mohammad, Tareq M.; Ali, Fatima S.; Nandy, Koushik; Zou, Youran; Stöhr, Robert; Agaimy, Abbas (Virchows Archiv, 2024)
With the increasing use of next generation sequencing in soft tissue pathology, particularly in neoplasms not fitting any World Health Organization (WHO) category, the spectrum of EWSR1 fusion-associated soft tissue neoplasms has been expanding significantly. Although recurrent EWSR1::ATF1 fusions were initially limited to a triad of mesenchymal neoplasms including clear cell sarcoma of soft tissue, angiomatoid fibrous histiocytoma and malignant gastrointestinal neuroectodermal tumor (MGNET), this family has been expanding. We herein describe 4 unclassified extra-abdominal soft tissue (n = 3) and bone (n = 1) neoplasms displaying epithelioid and round cell morphology and carrying an EWSR1::ATF1 fusion. Affected were 3 males and 1 female aged 20–56 years. All primary tumors were extra-abdominal and deep-seated (chest wall, mediastinum, deltoid, and parapharyngeal soft tissue). Their size ranged 4.4–7.5 cm (median, 6.2). One patient presented with constitutional symptoms. Surgery with (2) or without (1) neo/adjuvant therapy was the treatment. At last follow-up (8–21 months), 2 patients developed progressive disease (1 recurrence; 1 distant metastasis). The immunophenotype of these tumors is potentially misleading with variable expression of EMA (2 of 3), pankeratin (2 of 4), synaptophysin (2 of 3), MUC4 (1 of 3), and ALK (1 of 3). All tumors were negative for S100 and SOX10. These observations point to the existence of heretofore under-recognized group of epithelioid and round cell neoplasms of soft tissue and bone, driven by EWSR1::ATF1 fusions, but distinct from established EWSR1::ATF1-associated soft tissue entities. Their overall morphology and immunophenotype recapitulate that of the emerging EWSR1/FUS::CREB fusion associated intra-abdominal epithelioid/round cell neoplasms. Our cases point to a potentially aggressive clinical behavior. Recognizing this tumor type is mandatory to delineate any inherent biological and/or therapeutic distinctness from other, better-known sarcomas in the differential diagnosis including sclerosing epithelioid fibrosarcoma.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Ewing sarcoma; Genetic landscape; Mimics; Precision medicine; Profiling; Targeted next-generation sequencing

Exceptional response to neoadjuvant targeted therapy with the selective RET inhibitor selpercatinib in RET-fusion-associated sarcoma - Schrenk, Karin G.; Weschenfelder, Wolfram; Spiegel, Christian; Agaimy, Abbas; Stöhr, Robert; Hartmann, Arndt; Gassler, Nikolaus; Drescher, Robert; Freesmeyer, Martin; Malouhi, Amer; Buerckenmeyer, Florian; Aschenbach, Rene; et al. (Journal of Cancer Research and Clinical Oncology, 2022)
With the increasing use of next-generation sequencing, highly effective targeted therapies have been emerging as treatment options for several cancer types. Recurrent gene-fusions have been recognized in sarcomas; however, options for targeted therapy remain scarce. Here, we describe a case of a sarcoma, associated with a RET::TRIM33-fusion gene with an exceptional response to a neoadjuvant therapy with the selective RET inhibitor selpercatinib. Resected tumor revealed subtotal histopathologic response. This is the first report of successful targeted therapy with selpercatinib in RET-fusion-associated sarcomas. As new targeted therapies are under development, similar treatment options may become available for sarcoma patients.
CRIS-Team WoS Importer:2023-01-06

Expression of AR-V7 (Androgen receptor variant 7) protein in granular cytoplasmic structures is an independent prognostic factor in prostate cancer patients - König, Paul; Eckstein, Markus; Jung, Rudolf; Abdulrahman, Amer; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Hayashi, Jun; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (Cancers, 2020)
Prostate cancer (PCa) is the second most common cancer, causing morbidity and mortality among men world-wide. The expression of the androgen receptor (AR) and its splice variants is a crucial factor of prostate cancer biology that has not been comprehensively studied in PCa tumors. The aim of this study was to characterize the protein expression of the AR and its splice variant, AR-V7, and their subcellular distributions in PCa by immunohistochemistry and to correlate the results to the clinicopathological data and prognosis. Immunohistochemical staining for AR and AR-V7 was performed on a tissue microarray (TMA) with specimens from 410 PCa patients using an immunoreactive score (IRS) or only the percentage of AR-V7 staining in cytoplasmic granules. Nuclear or cytoplasmic AR staining was not associated with prognosis. AR-V7 staining was only occasionally observed in the nucleus. However, AR-V7 staining in the cytoplasm or in cytoplasmic granules was associated with relapse-free survival (RFS). AR-V7 staining of the cytoplasm was associated with a shorter RFS, whereas AR-V7 staining of cytoplasmic granules was associated with a longer RFS. In a multivariate Cox’s regression analysis, only negative (<5%) AR-V7 staining of cytoplasmic granules remained an independent prognostic factor for RFS (HR = 5.3; p = 0.006). In a further subgroup analysis by multivariate Cox’s regression analysis, AR-V7 was an independent prognostic factor in the following groups: age ≤ 65 (HR = 9.7; p = 0.029), negative CK20 staining (HR = 7.0; p = 0.008), and positive perineural invasion (HR = 3.7; p = 0.034). Altogether, AR-V7 protein in granular cytoplasmic structures is an independent prognostic factor for RFS in PCa patients.
CRIS-Team Scopus Importer:2020-09-25
Keywords: AR; AR-V7; Gleason score; Perineural invasion; Prognosis; Prostate cancer; Relapse-free survival; RFS

Expression of GP88 (Progranulin) Protein Is an Independent Prognostic Factor in Prostate Cancer Patients - Abdulrahman, Amer; Eckstein, Markus; Jung, Rudolf; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Yue, Binbin; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; et al. (Cancers, 2019)
Prostate cancer, the second most common cancer, is still a major cause of morbidity and mortality among men worldwide. The expression of the survival and proliferation factor progranulin (GP88) has not yet been comprehensively studied in PCa tumors. The aim of this study was to characterize GP88 protein expression in PCa by immunohistochemistry and to correlate the findings to the clinico-pathological data and prognosis. Immunohistochemical staining for GP88 was performed by TMA with samples from 442 PCa patients using an immunoreactive score (IRS). Altogether, 233 cases (52.7%) with negative GP88 staining (IRS < 2) and 209 cases (47.3%) with positive GP88 staining (IRS >= 2) were analyzed. A significant positive correlation was found for the GP88 IRS with the PSA value at prostatectomy and the cytoplasmic cytokeratin 20 IRS, whereas it was negatively associated with follow-up times. The association of GP88 staining with prognosis was further studied by survival analyses (Kaplan-Meier, univariate and multivariate Cox's regression analysis). Increased GP88 protein expression appeared as an independent prognostic factor for overall, disease-specific and relapse-free survival in all PCa patients. Interestingly, in the subgroup of younger PCa patients (<= 65 years), GP88 positivity was associated with a 3.8-fold (p = 0.004), a 6.0-fold (p = 0.008) and a 3.7-fold (p = 0.003) increased risk for death, disease-specific death and occurrence of a relapse, respectively. In the PCa subgroup with negative CK20 staining, GP88 positivity was associated with a 1.8-fold (p = 0.018) and a 2.8-fold increased risk for death and disease-specific death (p = 0.028). Altogether, GP88 protein positivity appears to be an independent prognostic factor for PCa patients.
CRIS-Team WoS Importer:2020-01-28

Extra-abdominal and intra-abdominal FET::CREM fusion mesenchymal neoplasms: comparative clinicopathological study of 9 new cases further supporting a distinct potentially aggressive sarcoma and report of novel sites - Agaimy, Abbas; Blakely, Morgan; Breimer, Gerben E.; Hölsken, Annett; Koppes, Sjors A.; Meidenbauer, Norbert; Rijken, Johannes A.; Schad, Arno; Simon, Adrian G.; Stöhr, Robert; Bishop, Justin A.; Din, Nasir Ud (Virchows Archiv, 2024)
With the wide use of RNA sequencing technologies, the family of FET::CREB fusion mesenchymal neoplasms has expanded rapidly to include potentially aggressive neoplasms, not fitting any well established WHO entity. Recently, a group of intra-abdominal FET(EWSR1/FUS)::CREB(CREM/ATF1) fused unclassified neoplasms has been reported followed by recent recognition of an analogous extra-abdominal category of unclassified neoplasms carrying EWSR1::ATF1 fusions. We describe 9 additional tumors (5 extra-abdominal and 4 abdominal) carrying an EWSR1::CREM (n = 8) and FUS::CREM (n = 1) fusion. Patients were 7 females and 2 males aged 10 to 75 years (median, 34). Extra-abdominal tumors originated in the head and neck (2 sinonasal, 1 orbital) and soft tissues (1 gluteal, 1 inguinal). Abdominal tumors involved stomach (2), mesentery (1), and kidney (1). Tumor size ranged from 3.5 to 11 cm (median, 6). Treatment was radical surgery with (5) or without (2) neo/adjuvant radio/chemotherapy. Extended follow-up of 5 patients (21–52 months; median, 24) showed an aggressive course in two (40%); one died of disseminated metastases 52 months after several intensified chemotherapy regimens, and one was alive with progressive abdominal disease at 21 months. The immunophenotype of the two subcohorts was significantly overlapping with variable expression of EMA (7 of 8), keratin AE1/AE3 (5 of 9), CD99 (4 of 7), MUC4 (2 of 8), ALK (3 of 8), synaptophysin (3 of 9), chromogranin (1 of 8), CD34 (3 of 6), CD30 (1 of 6), PAX8 (1 of 7), and inhibin (1 of 7), but no reactivity with desmin (0 of 8), S100 (0 of 8), and SOX10 (0 of 8). This series further solidifies the notion that FET::CREB fusions are not limited to the triad of angiomatoid fibrous histiocytoma, clear cell sarcoma, and malignant gastrointestinal neuroectodermal tumor, but characterize an emerging family of potentially aggressive neoplasms occurring at both intra- and extra-abdominal sites. These tumors underscore the promiscuity of the FET::CREB fusions and highlight the pivotal role of phenotype-oriented classification of these neoplasms that share the same genotype, still featuring significant biological and behavioral distinctness.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Constitutional symptoms; Ewing sarcoma; Genetic landscape; Next generation sequencing; Precision medicine; Profiling

FGFR3 Mutation Status and FGFR3 Expression in a Large Bladder Cancer Cohort Treated by Radical Cystectomy: Implications for Anti-FGFR3 Treatment? - van Rhijn, Bas W.G.; Mertens, Laura S.; Mayr, Roman; Bostrom, Peter J.; Real, Francisco X.; Zwarthoff, Ellen C.; Boormans, Joost L.; Abas, Cheno; van Leenders, Geert J.L.H.; Götz, Stefanie; Hippe, Katrin; Bertz, Simone; et al. (European Urology, 2020)
Oncogenic fibroblast growth factor receptor 3 (FGFR3) mutations were associated with favorable bladder cancer in a series of 1000 radical cystectomy cases. Moreover, patients with FGFR3 mutant tumors would be more likely to benefit from anti-FGFR3 therapy than patients with overexpression only.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Bladder; Cancer; Cystectomy; Expression; FGFR3; Mutation; Urothelial carcinoma

FGFR3::TACC3 fusions in head and neck carcinomas: a study of nine cases highlighting phenotypic heterogeneity, frequent HPV association, and a morphologically distinct subset in favor of a putative entity - Agaimy, Abbas; Antonescu, Cristina R.; Bell, Diana; Breimer, Gerben E.; Dermawan, Josephine K.; Kester, Lennart A.; Laco, Jan; Rijken, Johannes A.; Whaley, Rumeal D.; Stöhr, Robert; Cramer, Thomas; Bishop, Justin A. (Virchows Archiv, 2024)
The FGFR3::TACC3 fusion has been reported in subsets of diverse cancers including urothelial and squamous cell carcinomas (SCC). However, the morphology of FGFR3::TACC3-positive head and neck carcinomas has not been well studied and it is unclear if this fusion represents a random event, or if it might characterize a morphologically distinct tumor type. We describe nine FGFR3::TACC3 fusion–positive head and neck carcinomas affecting six males and three females aged 38 to 89 years (median, 59). The tumors originated in the sinonasal tract (n = 4), parotid gland (n = 2), and one case each in the oropharynx, submandibular gland, and larynx. At last follow-up (9–21 months; median, 11), four patients developed local recurrence and/or distant metastases, two died of disease at 11 and 12 months, one died of other cause, one was alive with disease, and two were disease-free. Three of six tumors harbored high risk oncogenic HPV infection (HPV33, HPV18, one unspecified). Histologically, three tumors revealed non-keratinizing transitional cell-like or non-descript morphology with variable mixed inflammatory infiltrate reminiscent of mucoepidermoid or DEK::AFF2 carcinoma (all were HPV-negative), and three were HPV-associated (all sinonasal) with multiphenotypic (1) and non-intestinal adenocarcinoma (2) pattern, respectively. One salivary gland tumor showed poorly cohesive large epithelioid cells with prominent background inflammation and expressed AR and GATA3, in line with a possible salivary duct carcinoma variant. Two tumors were conventional SCC. Targeted RNA sequencing revealed an in-frame FGFR3::TACC3 fusion in all cases. This series highlights heterogeneity of head and neck carcinomas harboring FGFR3::TACC3 fusions, which segregates into three categories: (1) unclassified HPV-negative category, morphologically distinct from SCC and other entities; (2) heterogeneous group of HPV-associated carcinomas; and (3) conventional SCC. A driver role of the FGFR3::TACC3 fusion in the first category (as a potential distinct entity) remains to be further studied. In the light of available FGFR-targeting therapies, delineation of these tumors and enhanced recognition is recommended.
CRIS-Team Scopus Importer:2024-10-25
Keywords: FGFR; Gene fusions; RNA sequencing; Sinonasal; Targeted therapy; Tyrosine kinase inhibitor

Frequency of GNAS mutation in intramuscular myxoma - Erber, Ramona; Stöhr, Robert; Haller, Florian; Hartmann, Arndt; Agaimy, Abbas (VIRCHOWS ARCHIV, 2019)
CRIS-Team WoS Importer:2019-09-27

Frequency of microsatellite instability (MSI) in upper tract urothelial carcinoma: comparison of the Bethesda panel and the Idylla MSI assay in a consecutively collected, multi-institutional cohort - Kullmann, Friederike; Strissel, Pamela; Strick, Reiner; Stöhr, Robert; Eckstein, Markus; Bertz, Simone; Wullich, Bernd; Sikic, Danijel; Wach, Sven; Taubert, Helge; Olbert, Peter; Heers, Hendrik; et al. (Journal of Clinical Pathology, 2021)
Aims Upper tract urothelial carcinoma (UTUC) is a rare malignancy with a poor prognosis which occurs sporadically or in few cases results from a genetic disorder called Lynch syndrome. Recently, examination of microsatellite instability (MSI) has gained importance as a biomarker: MSI tumours are associated with a better response to immunomodulative therapies. Limited data are known about the prevalence of MSI in UTUC. New detection methods using the fully automated Idylla MSI Assay facilitate analysis of increased patient numbers. Methods We investigated the frequency of MSI in a multi-institutional cohort of 243 consecutively collected UTUC samples using standard methodology (Bethesda panel), along with immunohistochemistry of mismatch repair (MMR) proteins. The same tumour cohort was retested using the Idylla MSI Assay by Biocartis. Results Using standard methodology, 230/243 tumours were detected as microsatellite stable (MSS), 4/243 tumours as MSI and 9/243 samples as invalid. In comparison, the Idylla MSI Assay identified four additional tumours as MSS, equalling 234/243 tumours; 4/243 were classified as MSI and only 5/243 cases as invalid. At the immunohistochemical level, MSI results were supported in all available cases with a loss in MMR proteins. The overall concordance between the standard and the Idylla MSI Assay was 98.35%. Time to result differed between 3 hours for Idylla MSI Assay and 2 days with the standard methodology. Conclusion Our data indicate a low incidence rate of MSI tumours in patients with UTUC. Furthermore, our findings highlight that Idylla MSI Assay can be applied as an alternative method of MSI analysis for UTUC.
CRIS-Team WoS Importer:2021-12-10

GAB1::ABL1 fusions define a distinctive soft tissue neoplasm, with variable perineurial differentiation, and a predilection for children and young adults - Agaimy, Abbas; Perret, Raul; Demicco, Elizabeth G.; Gross, John M.; Liu, Yajuan J.; Azmani, Rihab; Engelmann, Carsten; Schubart, Christoph; Seppet, Joosep; Stöhr, Robert; Le Loarer, François; Dickson, Brendan C. (Genes Chromosomes & Cancer, 2023)
Although well known as a fusion partner in hematological malignancies, fusion genes involving the ABL proto-oncogene 1 (ABL1), mapping to chromosomal region 9q34.12, have only been anecdotally reported in five soft tissue tumors. These neoplasms have been variously reported as perineurioma, angiofibroma, and solitary fibrous tumor, and all have harbored a GAB1::ABL1 gene fusion; however, the nosology and clinicopathological characteristics of soft tissue tumors carrying this rare fusion have not been delineated. We herein describe eight tumors containing the GAB1::ABL1 fusion and review previously reported cases in a series to define their morphological spectrum, address immunohistochemical evidence for a line of differentiation, with special reference to the presence or absence of a perineurial immunophenotype, and gather insight into their behavior. The patients included four females and four males, aged 13–37 years (median, 24 years). Two cases each originated in the shoulder area, trunk, hands, and lower extremities, with a size range of 1.5–8 cm (median, 3.4 cm). Four tumors were deep and four superficial. All tumors were morphologically similar, being composed of bland fibroblast-like spindle to ovoid cells diffusely arranged in a paucivascular fibrous to fibromyxoid stroma with variable resemblance to soft tissue perineurioma. Mitotic activity was generally low (0–8 mitoses in 10 high-power fields [HPFs]; median, 1). All lesions had at least focally infiltrative margins, but they otherwise lacked pleomorphism and necrosis. Immunohistochemistry showed focal reactivity for CD34 (5/7), epithelial membrane antigen (EMA) (3/8), claudin1 (2/3), GLUT1 (4/6), and S100 (2/7); other markers, including MUC4 (0/7), desmin (0/9), and smooth muscle actin (SMA) (0/4), were negative. RNA sequencing revealed a GAB1::ABL1 fusion in all cases with exon 6 of GAB1 fused to exon 2 of ABL1. Treatments included various forms of surgical intervention in seven cases; one tumor was biopsied only. Limited follow-up was available for five patients. One tumor regrew rapidly within 1 month to 1.5 cm after an initial marginal excision and was re-excised with close margins. Four patients were disease-free at 1, 3, 14, and 25 months of follow-up. Metastases have not, to date, been observed. This series characterizes “GAB1::ABL1 fusion-positive spindle cell neoplasm” as a distinct entity, with overlapping features with soft tissue perineurioma and predilection for children and young adults.
CRIS-Team Scopus Importer:2023-03-03
Keywords: ABL1; children; GAB1; gene fusion; perineurioma; tyrosine kinase receptors

Gene fusions are frequent in ACTH-secreting neuroendocrine neoplasms of the pancreas, but not in their non-pancreatic counterparts - Agaimy, Abbas; Kasajima, Atsuko; Stöhr, Robert; Haller, Florian; Schubart, Christoph; Tögel, Lars; Pfarr, Nicole; von Werder, Alexander; Pavel, Marianne Ellen; Sessa, Fausto; Uccella, Silvia; La Rosa, Stefano; et al. (Virchows Archiv, 2023)
Ectopic Cushing syndrome is a rare clinical disorder resulting from excessive adrenocorticotrophic hormone (ACTH) produced by non-pituitary neoplasms, mainly neuroendocrine neoplasms (NENs) of the lung, pancreas, and gastrointestinal tract, and other less common sites. The genetic background of ACTH-producing NENs has not been well studied. Inspired by an index case of ACTH-producing pancreatic NEN carrying a gene fusion, we postulated that ACTH-producing NENs might be enriched for gene fusions. We herein examined 21 ACTH-secreting NENs of the pancreas (10), lung (9), thymus (1), and kidney (1) using targeted RNA sequencing. The tumors were classified according to the most recent WHO classification as NET-G1/typical carcinoid (n = 4), NETG-2/atypical carcinoid (n = 14), and NET-G3 (n = 3). Overall, targeted RNA sequencing was successful in 11 cases (4 of 10 pancreatic tumors, 5 of 9 pulmonary tumors, and in the one renal and one thymic tumor). All four successfully tested pancreatic tumors revealed a gene fusion: two had a EWSR1::BEND2 and one case each had a KMT2A::BCOR and a TFG::ADGRG7 fusion, respectively. EWSR1 rearrangements were confirmed in both tumors with a EWSR1::BEND2 by FISH. Gene fusions were mutually exclusive with ATRX, DAXX, and MEN1 mutations (the most frequently mutated genes in NETs) in all four cases. Using RNA-based variant assessment (n = 16) or via the TSO500 panel (n = 5), no pathogenic BCOR mutations were detected in any of the cases. Taken together, gene fusions were detected in 4/4 (100%) pancreatic versus 0/7 (0%) non-pancreatic tumors, respectively. These results suggest a potential role for gene fusions in triggering the ACTH production in pancreatic NENs presenting with ectopic Cushing syndrome. While the exact mechanisms responsible for the ectopic ACTH secretion are beyond the scope of this study, overexpressed fusion proteins might be involved in promoter-mediated overexpression of pre-ACTH precursors in analogy to the mechanisms postulated for EWSR1::CREB1-mediated paraneoplastic phenomena in certain mesenchymal neoplasms. The genetic background of the ACTH-producing non-pancreatic NENs remains to be further studied.
CRIS-Team Scopus Importer:2023-02-03
Keywords: ACTH; Neuroendocrine tumor; NET; ectopic Cushing; EWSR1; BCOR fusion; BEND2 fusion; KMT2A

Heterogeneity-analysis of molecular subtypes of muscle-invasive bladder cancer and their precursor lesions in multiregion mapped whole-organ bladders - Weyerer, Veronika; Lange, Fabienne; Wullweber, Adrian; Stöhr, Robert; Bertz, Simone; Wach, S.; Taubert, Helge; Wullich, Bernd; Sikic, Danijel; Strissel, Pamela; Strick, Reiner; Hartmann, Arndt; et al. (UROLOGIC ONCOLOGY-SEMINARS AND ORIGINAL INVESTIGATIONS, 2020)
CRIS-Team WoS Importer:2021-01-15

HMGA2-WIF1 Rearrangements Characterize a Distinctive Subset of Salivary Pleomorphic Adenomas With Prominent Trabecular (Canalicular Adenoma-like) Morphology - Agaimy, Abbas; Ihrler, Stephan; Baneckova, Martina; Martineau, Valerie Costes; Mantsopoulos, Konstantinos; Hartmann, Arndt; Iro, Heinrich; Stöhr, Robert; Skalova, Alena (American Journal of Surgical Pathology, 2022)
Most of salivary gland neoplasms (benign and malignant) are characterized by recurrent gene fusions. Pleomorphic adenoma (PA), the most frequent salivary gland tumor, is driven by chromosomal rearrangements involving PLAG1 mapped to 8q12 and HMGA2 mapped to 12q13-15 in most cases. Multiple fusion partners have been identified including CTNNB1, FGFR1, LIFR, CHCHD7 and TCEA for PLAG1 fusions and NFIB, WIF1 and FHIT for HMGA2 fusions. To date, no data exist on the morphology of the few reported HMGA2-WIF1-rearranged PAs. We present 28 major salivary gland adenomas displaying distinctive trabecular and canalicular morphology associated with recurrent genotype. Patients were 15 females and 13 males aged 43 to 87 (median: 65). All tumors originated from the parotid. Their size range was 1 to 4 cm (mean: 2.3). Histologically, all tumors showed elongated or columnar cells arranged into bilayered to multilayered communicating and branching strands and trabeculae in a manner similar to canalicular adenoma of minor salivary glands or trabecular myoepithelioma with variable solid confluent intercalated duct-like areas. Fifteen tumors were exclusively canalicular/trabecular while 13 had intermingled or well-demarcated conventional (chondromyxoid) PA component comprising 5 to >50% of the tumor. The monomorphic areas expressed uniformly CK7 (28/28), vimentin (21/21), S100 (24/24), SOX10 (16/17) and variably p63 (8/21) and mammaglobin (6/16) but were negative with p40 (0/24), smooth muscle actin (0/24) and MUC4 (0/16). Targeted RNA sequencing revealed HMGA2 fusions in 14/16 (87%) assessable cases. Fusion partner was WIF1 (12), RPSAP52 (1) and HELB (1). Separate testing of the 2 components in 1 hybrid tumor showed same HMGA2/WIF1 fusion. HMGA2 immunohistochemistry was homogeneously positive in all cases including the 2 fusion-negative cases. A control cohort of 12 genuine canalicular adenomas revealed no HMGA2 fusions (0/4) and lacked HMGA2 immunoreactivity (0/12). This study highlights a distinctive variant in the spectrum of PA characterized by prominent trabecular and canalicular adenoma-like morphology. Our data confirm that canalicular adenomas in major salivary glands (either monomorphic or part of hybrid tumors) are distinct from canalicular adenoma of minor salivary glands. Their uniform genotype irrespective of presence or absence of a conventional PA component argues for classifying those tumors lacking a conventional PA component as "monomorphic variants of PA" rather than canalicular/basal cell adenomas, intercalated duct adenoma, trabecular myoepithelioma or true hybrid tumors.
CRIS-Team WoS Importer:2022-01-21

Identifying the Molecular Mechanisms Contributing to Progression, Metastasis, and Death in Low-grade Non–muscle-invasive Bladder Cancer: A Case Report - Weiß, Sarah; Hallmann, Steffen; Koch, Stefan; Eidt, Sebastian; Stöhr, Robert; Veltrup, Elke; Roggisch, Jenny; Wirtz, Ralph M.; Ecke, Thorsten H. (European Urology Open Science, 2021)
Transitional cell carcinoma of the bladder is a common malignancy with an estimated 549 393 new cases occurring in 2018 alone. Both non–muscle-invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC) show high recurrence and progression rates, and therefore impose a great burden on patients and health care systems. Current risk stratification and therapy strategies are predominantly based on clinical and histopathological findings for tumor stage and grade. The chemoresistance and metastasis of low-grade tumors suggest an incomplete understanding of disease mechanisms, despite numerous studies on differentiating molecular subtypes of bladder cancer to identify tumor drivers and potential therapeutic targets. We present a highly unusual course for a low-grade bladder tumor leading to metastasis and death, for which we used postmortem histopathological and molecular analyses to evaluate targetable alterations in key signaling pathways driving the underlying tumor biology.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Death; ERBB2; FGFR3; KRT20; Luminal subtype; Metastasis; Non–muscle-invasive bladder cancer

Immune Cell-Associated Protein Expression Helps to Predict Survival in Muscle-Invasive Urothelial Bladder Cancer Patients after Radical Cystectomy and Optional Adjuvant Chemotherapy - Taubert, Helge; Eckstein, Markus; Epple, Elena; Jung, Rudolf; Weigelt, Katrin; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Kehlen, Astrid; et al. (Cells, 2021)
Bladder cancer (BCa) is the tenth most commonly diagnosed malignant cancer worldwide. Although adjuvant chemotherapy following radical cystectomy is a common therapy for muscle invasive bladder cancer patients, no applicable biomarkers exist to predict which patients will benefit from chemotherapy. In this study, we examined three immune cell markers, the chemokine CC motif ligand 2 (CCL2), the pan macrophage marker cluster of differentiation 68 (CD68) and the M2 macrophage marker cluster of differentiation 163 (CD163), using immunohistochemistry to determine their predictive value for the chemotherapy response in different nodal stage (pN0 vs. pN1 + 2) and tumor stage subgroups (pT2 vs. pT3 + 4). The prognosis was studied in terms of the overall survival (OS), disease-specific survival (DSS), and recurrence-free-survival (RFS) in 168 muscle invasive BCa patients. Chemotherapy was associated with a poorer prognosis in patients with a higher expression of the immune markers CCL2 (RFS), CD68 (DSS and RFS), and CD163 (DSS and RFS) in the N0 group and with poorer survival in patients with a higher expression of the immune markers CCL2 (OS, DSS, and RFS), CD68 (OS, DSS, and RFS), and CD163 (OS, DSS, and RFS) in the pT2 group when compared with treatments without chemotherapy. In contrast, chemotherapy was associated with a better prognosis in patients with a low expression of the immune markers CCL2 (DSS and RFS), CD68 (OS, DSS, and RFS), and CD163 (OS) in the N1 + 2 group. In addition, chemotherapy was associated with improved survival in patients with a low expression of the immune marker CD68 (OS and DSS) and there was a trend for a better prognosis in patients with a low expression of CD163 (OS) in the pT3 + 4 group compared to patients not treated with chemotherapy. Interestingly, CD68 appeared to be the most applicable immune marker to stratify patients by the outcome of chemotherapy in the nodal stage and tumor stage groups. Overall, we suggest that, in addition to the clinical factors of tumor stage and nodal stage, it is also meaningful to consider the abundance of immune cells, such as macrophages, to better predict the response to chemotherapy for BCa patients after radical treatment.
CRIS-Team Scopus Importer:2021-02-12
Keywords: bladder cancer; CCL2; CD163; CD68; chemotherapy; immune cells; nodal stage; tumor stage

Immune Cell Gene Expression Signature is Associated with Improved Outcome in Muscle-Invasive Urothelial Bladder Cancer Patients Treated with Radical Cystectomy - Eckstein, Markus; Strissel, Pamela; Strick, Reiner; Weyerer, Veronika; Wirtz, Ralph M.; Pfannstiel, Carolin; Wullweber, Adrian; Lange, Fabienne; Erben, Philipp; Stöhr, Robert; Bertz, Simone; Geppert, Carol-Immanuel; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Intra-abdominal EWSR1/FUS-CREM-rearranged malignant epithelioid neoplasms: two cases of an emerging aggressive entity with emphasis on misleading immunophenotype - Agaimy, Abbas; Stöhr, Robert; Otto, Mike; Braesen, Jan Hinrich; Pfarr, Nicole; Konukiewitz, Bjoern; Kasajima, Atsuko; Hartmann, Arndt; Kloeppel, Guenter (Virchows Archiv, 2021)
CREB family (CREB1, ATF1, and CREM) gene fusions are defining markers in diverse mesenchymal neoplasms (clear cell sarcoma, angiomatoid fibrous histiocytoma, and others). However, neoplasms harboring EWSR1-CREM/FUS-CREM fusions are rare and poorly characterized. We describe two cases (55-year-old male with 7.5 cm renal mass and 32-year-old female with 5.5 cm mesenteric mass) illustrating their misleading immunophenotypes. Histologically, both showed eosinophilic and focally clear epithelioid cells arranged into sheets, nests, and trabeculae. Immunohistochemistry showed ALK, EMA, and AE1/AE3 immunoreactivity suggesting ALK-rearranged renal cell carcinoma (Case 1) and coexpression of keratin, EMA, synaptophysin, and chromogranin-A, suggesting neuroendocrine neoplasm (Case 2). Targeted RNA sequencing revealed EWSR1-CREM (Case 1) and FUS-CREM (Case 2) fusions. These cases add to the spectrum of CREM fusion-positive intra-abdominal epithelioid neoplasms. Their unusual immunophenotype and unexpected sites represent major pitfalls, underline a wide differential diagnosis, and emphasize the value of molecular testing in correctly diagnosing them.
CRIS-Team Scopus Importer:2021-07-16
Keywords: ALK; CREB; CREM; EWSR1; FUS; Mesentery; Neuroendocrine; Paraganglioma; Primary renal sarcoma; RCC

KRAS codon 12 mutations characterize a subset of de novo proliferating “metaplastic” Warthin tumors - Agaimy, Abbas; Mantsopoulos, Konstantinos; Iro, Heinrich; Stöhr, Robert (Virchows Archiv, 2023)
Warthin tumor (WT; synonym: cystadenolymphoma) represents one of the most frequent salivary gland tumors with a frequency equaling or even outnumbering that of pleomorphic adenomas in some series. Histologically, the tumor displays tall columnar oncocytic cells, arranged into two cell-thick layers lining variably cystic glands within an organoid lymphoid stroma. Tumors with exuberant squamous metaplasia in response to FNA-induced or other types of tissue injury/infarction have been referred to as “metaplastic WTs.” However, the same terminology was used for tumors with variable mucinous cell and solid or stratified epidermoid proliferations (occasionally mimicking mucoepidermoid carcinoma), although the “metaplasia concept” has never been proven for the latter. We herein investigated 22 WTs showing prominent mucoepidermoid-like or solid oncocytoma-like proliferations without prior FNA or histological evidence of infarction/ trauma using the TruSight Tumor 15 gene panel and KRAS pyrosequencing. As a control, we tested 11 conventional WTs. No statistically significant differences were observed between the two subcohorts regarding patient’s age and tumor size. Six of 22 (27%) proliferating/ metaplastic WTs revealed oncogenic KRAS mutations clustering at codon 12 (exon 2), while all conventional tumors lacked these mutations. Our findings are in line with a neoplastic nature of the epidermoid/ mucoepidermoid proliferations in non-injured “metaplastic” Warthin tumors. We propose the descriptive term “de novo proliferating Warthin tumor” for this variant to distinguish it from infarcted/inflamed genuine metaplastic Warthin tumor.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Cystadenolymphoma; KRAS mutations; Metaplastic Warthin tumor; Mucoepidermoid carcinoma; Salivary glands; Warthin tumor

Langerhans Cell Histiocytosis Associated with Renal Cell Carcinoma Is a Neoplastic Process: Clinicopathologic and Molecular Study of 7 Cases - Agaimy, Abbas; Bonert, Michael; Naqvi, Asghar; Wang, Chunjie; Trpkov, Kiril; Dettmar, Peer; Wintzer, Hanns Olof; Stöhr, Robert; Hes, Ondřej; Williamson, Sean R.; Gibson, Ian W.; Hartmann, Arndt (American Journal of Surgical Pathology, 2020)
Langerhans cell histiocytosis (LCH) is a rare histiocytic disorder composed of Langerhans cells admixed with reactive mononuclear and granulocytic cells, associated with prominent eosinophils. LCH is considered a neoplasm, driven in most cases by oncogenic RAS/RAF/MEK/ERK pathway mutations. The disease predominantly affects children. Urinary system involvement has rarely been reported in a multisystem disease setting. We describe 7 patients who presented with LCH occurring within (6 cases) or after (1 case) a resected clear cell (n=6) or clear cell papillary (n=1) renal cell carcinoma (RCC), identified prospectively in our routine and consultation files (2012 to 2019). The patients included 5 women and 2 men, with a median age of 54 years (range, 39 to 73 y), none with a history of LCH or LCH manifestations before the time of RCC diagnosis. The median size of the RCC was 3.5 cm (range, 1.8 to 8.3 cm). Treatment included partial (5 cases), or radical (2 cases) nephrectomy. All RCCs on gross examination showed at least focal cystic changes and were low grade (World Health Organization [WHO]/International Society of Urologic Pathologists [ISUP] grade 1 to 2). The LCH foci were detected as incidental histological finding within the resected RCC in all six cases and they were limited to few high-power fields (<2 mm2) in 5 of 6 cases, but in the sixth case, they occupied almost the entire clear cell papillary RCC (2 cm nodule). No LCH manifestations were detected in the normal kidney or in perinephric fat. The seventh patient developed LCH within inguinal deep soft tissue followed by systemic manifestations 6 years after clear cell RCC. Langerhans cell immunophenotype was supported by the reactivity for S-100, CD1a, and langerin and by the negative pankeratin. Successful pyrosequencing of microdissected LCH DNA revealed the V600E BRAF mutation in all 6 cases of LCH within RCC. To our knowledge, only 3 similar cases were published since 1980; the only case tested for BRAF mutation showed wild-type BRAF. This is the first study analyzing the morphologic and genetic features of a cohort of LCH associated with RCC. In our experience, these cases may be underrecognized in practice, or may erroneously be diagnosed as RCC dedifferentiation or high-grade sarcomatoid transformation. Finally, the detection of BRAF mutation further confirms that LCH in this setting is indeed a neoplasm, rather than a reactive lesion.
CRIS-Team Scopus Importer:2020-12-04
Keywords: BRAF V600E; concurrent; kidney; Langerhans cell histiocytosis; RCC; renal cell carcinoma

Lipomatous Solitary Fibrous Tumors Harbor Rare NAB2-STAT6 Fusion Variants and Show Up-Regulation of the Gene PPARG, Encoding for a Regulator of Adipocyte Differentiation - Haller, Florian; Schlieben, Lea D.; Ferrazzi, Fulvia; Michal, Michael; Stöhr, Robert; Moskalev, Evgeny; Bieg, Matthias; Bovée, Judith V.M.G.; Ströbel, Philip; Ishaque, Naveed; Grützmann, Robert; Meidenbauer, Norbert; et al. (American Journal of Pathology, 2021)
Solitary fibrous tumors (SFTs) harbor activating NAB2-STAT6 gene fusions. Different variants of the NAB2-STAT6 gene fusion have been associated with distinct clinicopathologic features. Lipomatous SFTs are a morphologic variant of SFTs, characterized by a fat-forming tumor component. Our aim was to evaluate NAB2-STAT6 fusion variants and to further study the molecular genetic features in a cohort of lipomatous SFTs. A hybrid-capture–based next-generation sequencing panel was employed to detect NAB2-STAT6 gene fusions at the RNA level. In addition, the RNA expression levels of 507 genes were evaluated using this panel, and were compared with a control cohort of nonlipomatous SFTs. Notably, 5 of 11 (45%) of lipomatous SFTs in the current series harbored the uncommon NAB2 exon 4–STAT6 exon 4 gene fusion variant, which is observed in only 0.9% to 1.4% of nonlipomatous SFTs. Furthermore, lipomatous SFTs displayed significant differences in gene expression compared with their nonlipomatous counterparts, including up-regulation of the gene peroxisome proliferator activated receptor-γ (PPARG). Peroxisome proliferator activated receptor-γ is a nuclear receptor regulating adipocyte differentiation, providing a possible explanation for the fat-forming component in lipomatous SFTs. In summary, the current study provides a possible molecular genetic basis for the distinct morphologic features of lipomatous SFTs.
CRIS-Team Scopus Importer:2021-06-04

Machine Learning-Supported Diagnosis of Small Blue Round Cell Sarcomas Using Targeted RNA Sequencing. - Schlieben, Lea D.; Carta, Maria Giulia; Moskalev, Evgeny; Stöhr, Robert; Metzler, Markus; Besendörfer, Manuel; Meidenbauer, Norbert; Semrau, Sabine; Janka, Rolf Matthias; Grützmann, Robert; Wiemann, Stefan; Hartmann, Arndt; et al. (Journal of Molecular Diagnostics, 2024)
Small blue round cell sarcomas (SBRCSs) are a heterogeneous group of tumors with overlapping morphologic features but markedly varying prognosis. They are characterized by distinct chromosomal alterations, particularly rearrangements leading to gene fusions, whose detection currently represents the most reliable diagnostic marker. Ewing sarcomas are the most common SBRCSs, defined by gene fusions involving EWSR1 and transcription factors of the ETS family, and the most frequent non-EWSR1-rearranged SBRCSs harbor a CIC rearrangement. Unfortunately, currently the identification of CIC::DUX4 translocation events, the most common CIC rearrangement, is challenging. Here, we present a machine-learning approach to support SBRCS diagnosis that relies on gene expression profiles measured via targeted sequencing. The analyses on a curated cohort of 69 soft-tissue tumors showed markedly distinct expression patterns for SBRCS subgroups. A random forest classifier trained on Ewing sarcoma and CIC-rearranged cases predicted probabilities of being CIC-rearranged >0.9 for CIC-rearranged-like sarcomas and <0.6 for other SBRCSs. Testing on a retrospective cohort of 1335 routine diagnostic cases identified 15 candidate CIC-rearranged tumors with a probability >0.75, all of which were supported by expert histopathologic reassessment. Furthermore, the multigene random forest classifier appeared advantageous over using high ETV4 expression alone, previously proposed as a surrogate to identify CIC rearrangement. Taken together, the expression-based classifier can offer valuable support for SBRCS pathologic diagnosis.
EVALuna2:565265

Malignant teratoid tumor of the thyroid gland: an aggressive primitive multiphenotypic malignancy showing organotypical elements and frequent DICER1 alterations—is the term “thyroblastoma” more appropriate? - Agaimy, Abbas; Witkowski, Leora; Stöhr, Robert; Cuenca, Joseph Christopher Castillo; González-Muller, Carlos Alberto; Brütting, Alfred; Bährle, Markus; Mantsopoulos, Konstantinos; Amin, Randa M.S.; Hartmann, Arndt; Metzler, Markus; Amr, Samir S.; et al. (Virchows Archiv, 2020)
Primary thyroid teratomas are exceedingly rare. Mature and immature variants recapitulate their gonadal counterparts (predilection for infants/children, triphasic germ layer differentiation, and favorable outcome). On the other hand, the so-called malignant teratomas affect predominantly adults and elderly, are highly aggressive, and, according to a few published cases, harbor DICER1 mutations. We describe three highly aggressive sporadic malignant teratoid thyroid tumors in 2 females (17 and 45 years) and one male (17 years). Histology showed triphasic neoplasms composed of solid nests of small primitive monomorphic cells embedded in a cellular stroma with primitive immature rhabdomyosarcoma-like (2) or pleomorphic sarcoma-like (1) phenotype. The third component was represented by TTF1+/PAX8+ primitive teratoid epithelial tubules reminiscent of primitive thyroid follicles and/or Wilms tumor, admixed with scattered respiratory- or enteric-type tubules, neuroepithelial rosettes, and fetal-type squamoid nests. Foci of cartilage were seen in two cases, but none contained mature organoid adult-type tissue or skin adnexa. SALL4 was expressed in the small cell (2) and stromal (1) component. Other germ cell markers were negative. Molecular testing revealed a known “hotspot” pathogenic DICER1 mutation in two cases. In addition, case 1 had a missense TP53 variant. This type of thyroid malignancy is distinct from genuine teratomas. The immunoprofile suggests primitive thyroid- or branchial cleft-like differentiation. Given that “blastoma” is a well-accepted terminology in the spectrum of DICER1-associated malignancies, the term “thyroblastoma” might be more convenient for these malignant teratoid tumors of the thyroid gland. Relationship of thyroblastoma to the DICER1 syndrome remains to be addressed.
CRIS-Team Scopus Importer:2020-06-16
Keywords: DICER1; Germ cell tumor; Head and neck; Malignant teratoma; Rhabdomyosarcoma; Teratocarcinosarcoma; Thyroblastoma; Thyroid

Met amplification in non‐small cell lung cancer (Nsclc)— a consecutive evaluation using next‐generation sequencing (ngs) in a real‐world setting - Schubart, Christoph; Stöhr, Robert; Tögel, Lars; Fuchs, Florian; Sirbu, Horia; Seitz, Gerhard; Seggewiss‐bernhardt, Ruth; Leistner, Rumo; Sterlacci, William; Seidl, Christoph; Mugler, Michael; Kapp, Markus; et al. (Cancers, 2021)
In non‐small cell lung cancer (NSCLC), approximately 1–3% of cases harbor an increased gene copy number (GCN) of the MET gene. This alteration can be due to de novo amplification of the MET gene or can represent a secondary resistance mechanism in response to targeted therapies. To date, the gold standard method to evaluate the GCN of MET is fluorescence in situ hybridization (FISH). However, next‐generation sequencing (NGS) is becoming more relevant to optimize therapy by revealing the mutational profile of each NSCLC. Using evaluable n = 205 NSCLC cases of a consecutive cohort, this study addressed the question of whether an amplicon based NGS assay can completely replace the FISH method regarding the classification of MET GCN status. Out of the 205 evaluable cases, only n = 9 cases (43.7%) of n = 16 high‐level MET amplified cases assessed by FISH were classified as amplified by NGS. Cases harboring a MET GCN >10 showed the best concordance when comparing FISH versus NGS (80%). This study confirms that an amplicon‐based NGS assessment of the MET GCN detects high‐level MET amplified cases harboring a MET GCN >10 but fails to detect the various facets of MET gene amplification in the context of a therapy‐induced resistance mechanism.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Amplification; Fluorescence in situ hybridization; MET; MET inhibitor; Next‐generation sequencing; NSCLC; Precision medicine; Resistance mechanism

Molecular Composition of Genomic TMPRSS2-ERG Rearrangements in Prostate Cancer - Krumbholz, Manuela; Agaimy, Abbas; Stöhr, Robert; Burger, Maximilian; Wach, Sven; Taubert, Helge; Wullich, Bernd; Hartmann, Arndt; Metzler, Markus (Disease Markers, 2019)
There is increasing interest in the use of cell-free circulating tumor DNA (ctDNA) as a serum marker for therapy assessment in prostate cancer patients. Prostate cancer is characterized by relatively low numbers of mutations, and, in contrast to many other common epithelial cancers, commercially available single nucleotide mutation assays for quantification of ctDNA are insufficient for therapy assessment in this disease. However, prostate cancer shares some similarity with translocation-affected mesenchymal tumors (e.g., leukemia and Ewing sarcoma), which are common in pediatric oncology, where chromosomal translocations are used as biomarkers for quantification of the tumor burden. Approximately 50% of prostate cancers carry a chromosomal translocation resulting in generation of the TMPRSS2-ERG fusion gene, which is unique to the tumor cells of each individual patient because of variability in the fusion breakpoint sites. In the present study, we examined the structural preconditions for TMPRSS2-ERG fusion sites in comparison with mesenchymal tumors in pediatric patients to determine whether the sequence composition is suitable for the establishment of tumor-specific quantification assays in prostate cancer patients. Genomic repeat elements represent potential obstacles to establishment of quantification assays, and we found similar proportions of repeat elements at fusion sites in prostate cancer to those reported for mesenchymal tumors, where genomic fusion sequences are established as biomarkers. Our data support the development of the TMPRSS2-ERG fusion gene as a noninvasive tumor marker for therapy assessment, risk stratification, and relapse detection to improve personalized therapy strategies for patients with prostate cancer.
CRIS-Team WoS Importer:2020-01-07

Molecular Subtyping of Invasive Breast Cancer Using a PAM50-Based Multigene Expression Test-Comparison with Molecular-Like Subtyping by Tumor Grade/Immunohistochemistry and Influence on Oncologist's Decision on Systemic Therapy in a Real-World Setting - Erber, Ramona; Angeloni, Miriam; Stöhr, Robert; Lux, Michael P.; Ulbrich-Gebauer, Daniel; Pelz, Enrico; Bankfalvi, Agnes; Schmid, Kurt W.; Walter, Robert F. H.; Vetter, Martina; Thomssen, Christoph; Mayr, Doris; et al. (International Journal of Molecular Sciences, 2022)
In intermediate risk hormone receptor (HR) positive, HER2 negative breast cancer (BC), the decision regarding adjuvant chemotherapy might be facilitated by multigene expression tests. In all, 142 intermediate risk BCs were investigated using the PAM50-based multigene expression test Prosigna (R) in a prospective multicentric study. In 119/142 cases, Prosigna (R) molecular subtyping was compared with local and two central (C1 and C6) molecular-like subtypes relying on both immunohistochemistry (IHC; HRs, HER2, Ki-67) and IHC + tumor grade (IHC+G) subtyping. According to local IHC, 35.4% were Luminal A-like and 64.6% Luminal B-like subtypes (local IHC+G subtype: 31.9% Luminal A-like; 68.1% Luminal B-like). In contrast to local and C1 subtyping, C6 classified >2/3 of cases as Luminal A-like. Pairwise agreement between Prosigna (R) subtyping and molecular-like subtypes was fair to moderate depending on molecular-like subtyping method and center. The best agreement was observed between Prosigna (R) (53.8% Luminal A; 44.5% Luminal B) and C1 surrogate subtyping (Cohen's kappa = 0.455). Adjuvant chemotherapy was suggested to 44.2% and 88.6% of Prosigna (R) Luminal A and Luminal B cases, respectively. Out of all Luminal A-like cases (locally IHC/IHC+G subtyping), adjuvant chemotherapy was recommended if Prosigna (R) testing classified as Prosigna (R) Luminal A at high / intermediate risk or upgraded to Prosigna (R) Luminal B.
CRIS-Team WoS Importer:2022-08-26

Multicenter evaluation of an automated, multiplex, RNA-based molecular assay for detection of ALK, ROS1, RET fusions and MET exon 14 skipping in NSCLC - Melchior, Linea; Hirschmann, Astrid; Hofman, Paul; Bontoux, Christophe; Concha, Angel; Mrabet-Dahbi, Salima; Vannuffel, Pascal; Watkin, Emmanuel; Putzová, Martina; Scarpino, Stefania; Cayre, Anne; Martin, Paloma; et al. (Virchows Archiv, 2024)
The current study assessed the performance of the fully automated RT-PCR-based Idylla™ GeneFusion Assay, which simultaneously covers the advanced non-small cell lung carcinoma (aNSCLC) actionable ALK, ROS1, RET, and MET exon 14 rearrangements, in a routine clinical setting involving 12 European clinical centers. The Idylla™ GeneFusion Assay detects fusions using fusion-specific as well as expression imbalance detection, the latter enabling detection of uncommon fusions not covered by fusion-specific assays. In total, 326 archival aNSCLC formalin-fixed paraffin-embedded (FFPE) samples were included of which 44% were resected specimen, 46% tissue biopsies, and 9% cytological specimen. With a total of 179 biomarker-positive cases (i.e., 85 ALK, 33 ROS1, 20 RET fusions and 41 MET exon 14 skipping), this is one of the largest fusion-positive datasets ever tested. The results of the Idylla™ GeneFusion Assay were compared with earlier results of routine reference technologies including fluorescence in situ hybridization, immunohistochemistry, reverse-transcription polymerase chain reaction, and next-generation sequencing, establishing a high sensitivity/specificity of 96.1%/99.6% for ALK, 96.7%/99.0% for ROS1, 100%/99.3% for RET fusion, and 92.5%/99.6% for MET exon 14 skipping, and a low failure rate (0.9%). The Idylla™ GeneFusion Assay was found to be a reliable, sensitive, and specific tool for routine detection of ALK, ROS1, RET fusions and MET exon 14 skipping. Given its short turnaround time of about 3 h, it is a time-efficient upfront screening tool in FFPE samples, supporting rapid clinical decision making. Moreover, expression-imbalance-based detection of potentially novel fusions may be easily verified with other routine technologies without delaying treatment initiation.
CRIS-Team Scopus Importer:2024-05-10
Keywords: ALK fusion; Idylla; MET exon 14 skipping; NSCLC; RET fusion; ROS1 fusion

Multinational proficiency tests for EGFR exon 20 insertions reveal that the assay design matters - Ihle, Michaela A.; Heydt, Carina; Schultheis, Anne Maria; Stöhr, Robert; Haller, Florian; Herold, Sylvia; Aust, Daniela; Dietmaier, Wolfgang; Evert, Matthias; Eszlinger, Markus; Haak, Anja; Laßmann, Silke; et al. (Scientific Reports, 2024)
Insertion mutations in exon 20 of the epidermal growth factor receptor gene (EGFR exon20ins) are rare, heterogeneous alterations observed in non-small cell lung cancer (NSCLC). With a few exceptions, they are associated with primary resistance to established EGFR tyrosine kinase inhibitors (TKIs). As patients carrying EGFR exon20ins may be eligible for treatment with novel therapeutics—the bispecific antibody amivantamab, the TKI mobocertinib, or potential future innovations—they need to be identified reliably in clinical practice for which quality-based routine genetic testing is crucial. Spearheaded by the German Quality Assurance Initiative Pathology two international proficiency tests were run, assessing the performance of 104 participating institutes detecting EGFR exon20ins in tissue and/or plasma samples. EGFR exon20ins were most reliably identified using next-generation sequencing (NGS). Interestingly, success rates of institutes using commercially available mutation-/allele-specific quantitative (q)PCR were below 30% for tissue samples and 0% for plasma samples. Most of these mutation-/allele-specific (q)PCR assays are not designed to detect the whole spectrum of EGFR exon20ins mutations leading to false negative results. These data suggest that NGS is a suitable method to detect EGFR exon20ins in various types of patient samples and is superior to the detection spectrum of commercially available assays.
CRIS-Team Scopus Importer:2024-06-14

NAB2::STAT6 fusions and genome-wide DNA methylation profiling: Predictors of patient outcomes in meningeal solitary fibrous tumors - Eschbacher, Kathryn L.; Tran, Quynh T.; Moskalev, Evgeny; Jenkins, Sarah; Fritchie, Karen; Stöhr, Robert; Caron, Alissa; Link, Michael J.; Brown, Paul D.; Guajardo, Andrew; Brat, Daniel J.; Wu, Ashley; et al. (Brain Pathology, 2024)
Meningeal solitary fibrous tumors (SFT) are rare and have a high frequency of local recurrence and distant metastasis. In a cohort of 126 patients (57 female, 69 male; mean age at surgery 53.0 years) with pathologically confirmed meningeal SFTs with extended clinical follow-up (median 9.9 years; range 15 days–43 years), we performed extensive molecular characterization including genome-wide DNA methylation profiling (n = 80) and targeted TERT promoter mutation testing (n = 98). Associations were examined with NAB2::STAT6 fusion status (n = 101 cases; 51 = ex5-7::ex16-17, 26 = ex4::ex2-3; 12 = ex2-3::exANY/other and 12 = no fusion) and placed in the context of 2021 Central Nervous System (CNS) WHO grade. NAB2::STAT6 fusion breakpoints (fusion type) were significantly associated with metastasis-free survival (MFS) (p = 0.03) and, on multivariate analysis, disease-specific survival (DSS) when adjusting for CNS WHO grade (p = 0.03). DNA methylation profiling revealed three distinct clusters: Cluster 1 (n = 38), Cluster 2 (n = 22), and Cluster 3 (n = 20). Methylation clusters were significantly associated with fusion type (p < 0.001), with Cluster 2 harboring ex4::ex2-3 fusion in 16 (of 20; 80.0%), nearly all TERT promoter mutations (7 of 8; 87.5%), and predominantly an “SFT” histologic phenotype (15 of 22; 68.2%). Clusters 1 and 3 were less distinct, both dominated by tumors having ex5-7::ex16-17 fusion (respectively, 25 of 33; 75.8%, and 12 of 18; 66.7%) and with variable histological phenotypes. Methylation clusters were significantly associated with MFS (p = 0.027), but not overall survival (OS). In summary, NAB2::STAT6 fusion type was significantly associated with MFS and DSS, suggesting that tumors with an ex5::ex16-17 fusion may have inferior patient outcomes. Methylation clusters were significantly associated with fusion type, TERT promoter mutation status, histologic phenotype, and MFS.
CRIS-Team Scopus Importer:2024-04-12
Keywords: CNS WHO grade; meningeal solitary fibrous tumor; NAB2::STAT6; solitary fibrous tumor; TERT

Nodular fasciitis: a case series unveiling novel and rare gene fusions, including two cases with aggressive clinical behavior - Saoud, Carla; Agaimy, Abbas; Stöhr, Robert; Michal, Michael; Wang, Scott Kuan Wen; Mandavilli, Srinivas; Charville, Gregory W.; Linos, Konstantinos (Virchows Archiv, 2025)
Nodular fasciitis is a benign myofibroblastic tumor characterized by rapid growth and spontaneous regression. While nodular fasciitis is typically an indolent process, rare cases with benign morphologic features have developed metastases. Conversely, nodular fasciitis with malignant histologic features and benign clinical course have also been reported. In this study, we present seven nodular fasciitis cases with novel USP6 gene fusion partners, in addition to two cases with rare fusions that displayed aggressive clinical behavior. The cohort comprised five females and four males with a median age of 36 years (range 13–59). Tumors were located in the forearm (n = 3), thigh (n = 2), and shoulder, abdominal wall, chest wall, and oral cavity (one each), ranging from 1.4 to 24.0 cm in size (median, 2.2 cm). Except for the clinically aggressive cases, patients presented with painless masses of varying onset from days to months. Of the clinically aggressive cases, one patient presented with a slowly growing subfascial thigh/hip mass over nine years, leading to erosion of the femur and pelvis; the other presented with a painful subfascial thigh mass of several months' duration. Histologically, all cases, including the clinically aggressive ones, showed conventional nodular fasciitis features without nuclear pleomorphism or atypical mitotic figures; one case with aggressive clinical behavior exhibited focal infarction-type necrosis. Break-apart FISH analysis using USP6 flanking probes failed to detect USP6 rearrangement in two cases (false negatives) and was inconclusive in one case. Next-generation RNA sequencing identified USP6 fusions in all cases. The clinically aggressive cases showed fusions with COL1A1 (exon 1) and PPP6R3 (exon 1), while novel fusions were identified in the remaining cases including EIF4A1 (exon 1), FILIP1L (exon 2), NF1 (exon 33), OMD (exon 1), PFN1 (exon 1), RLIM (exon 1), and SETD5 (exon 1). Six patients underwent surgical resection; three were managed conservatively, with two experiencing spontaneous tumor resolution. Of the clinically aggressive cases, one patient had progression of the tumor with erosion of the underlying bone, and the second patient developed local recurrence at 14 months and lung metastasis at 19 months, ultimately dying of disease at 22 months. The remaining patients showed no recurrence or metastasis. Our findings expand the spectrum of USP6 gene fusion partners in nodular fasciitis and, for the first time, report cases with conventional morphology exhibiting aggressive behavior, including death. These observations raise the question of whether a subset of deep lesions with conventional nodular fasciitis histology but unusual clinical features, such as large tumor size, represents malignant nodular fasciitis or alternatively a nodular fasciitis-like myofibroblastic sarcoma.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Aggressive behavior; Nodular fasciitis; Novel gene fusions; Rare partners

Novel NCOA2/3-rearranged low-grade fibroblastic spindle cell tumors: A report of five cases - Bakhshwin, Ahmed; Armstrong, Susan M.; Duckworth, Lauren A.; Stöhr, Robert; Konishi, Eiichi; Rubin, Brian P.; Fritchie, Karen J.; Dickson, Brendan C.; Agaimy, Abbas; Dermawan, Josephine K. (Genes Chromosomes & Cancer, 2023)
Spindle cell mesenchymal neoplasms are a diverse and often challenging diagnostic group. While morphological impression is sufficient for some diagnoses, increasingly immunohistochemical and even molecular data is required to render an accurate diagnosis, which can lead to the characterization of new entities. We describe five cases of novel mesenchymal neoplasms with rearrangements in the NCOA2 and NCOA3 genes partnered with either CTCF or CRTC1. Three tumors occurred in the head and neck (palate, auditory canal), while the other two were in visceral organs (lung, urinary bladder). All cases occurred in adults (range 33–86) with a median age of 42 and fairly even sex distribution = (male-to-female = 3:2). Morphologically, they had similar features consisting of monotonous, bland spindle to ovoid cells with fascicular and reticular arrangements in a myxohyaline to collagenous stroma. However, immunophenotypically they had essentially a null phenotype, with only two tumors staining partially for CD34 and smooth muscle actin. Targeted RNA sequencing detected in-frame CTCF::NCOA2 (one case), CRTC1::NCOA2 (two cases), and CTCF::NCOA3 (two cases) fusions. Treatment was surgical resection in all cases. Local recurrence and/or distant metastases were not observed in any case (median follow-up, 7.5 months; range, 2–19 months). Given their morphologic, immunohistochemical, and molecular similarities, we believe that these cases may represent an emerging family of low-grade NCOA2/3-rearranged fibroblastic spindle cell neoplasms.
CRIS-Team Scopus Importer:2023-09-29
Keywords: CRTC1; CTCF; mesenchymal tumor; NCOA2; NCOA3

NR4A3 fusions characterize a distinctive peritoneal mesothelial neoplasm of uncertain biological potential with pure adenomatoid/microcystic morphology - Agaimy, Abbas; Brcic, Luka; Briski, Laurence M.; Hung, Yin P.; Michal, Michael; Michal, Michal; Nielsen, G. Petur; Stöhr, Robert; Rosenberg, Andrew E. (Genes Chromosomes & Cancer, 2022)
A focal adenomatoid-microcystic pattern is not uncommon in peritoneal mesothelioma, but tumors composed almost exclusively of this pattern are distinctly rare and have not been well characterized. A small subset of mesotheliomas (mostly in children and young adults) are characterized by gene fusions including EWSR1/FUS::ATF1, EWSR1::YY1, and NTRK and ALK rearrangements, and often have epithelioid morphology. Herein, we describe five peritoneal mesothelial neoplasms (identified via molecular screening of seven histologically similar tumors) that are pure adenomatoid/microcystic in morphology and unified by the presence of an NR4A3 fusion. Patients were three males and two females aged 31-70 years (median, 40 years). Three presented with multifocal/diffuse and two with a localized disease. The size of the individual lesions ranged from 1.5 to 8 cm (median, 4.7). The unifocal lesions originated in the small bowel mesentery and the mesosigmoid. Treatment included surgery, either alone (three) or combined with hyperthermic intraperitoneal chemotherapy (two), and neoadjuvant or adjuvant chemotherapy (one case each). At the last follow-up (6-13 months), all five patients were alive and disease-free. All tumors were morphologically similar, characterized by extensive sieve-like microcystic growth with bland-looking flattened cells lining variably sized microcystic spaces and lacked a conventional epithelioid or sarcomatoid component. Immunohistochemistry confirmed mesothelial differentiation, but most cases showed limited expression of D2-40 and calretinin. Targeted RNA sequencing revealed an NR4A3 fusion (fusion partners were EWSR1 in three cases and CITED2 and NIPBL in one case each). The nosology and behavior of this morphomolecularly defined novel peritoneal mesothelial neoplasm of uncertain biological potential and its distinction from adenomatoid variants of conventional mesothelioma merit further delineation as more cases become recognized.
CRIS-Team WoS Importer:2023-01-20

NSD3-NUTM1-rearranged carcinoma of the median neck/thyroid bed developing after recent thyroidectomy for sclerosing mucoepidermoid carcinoma with eosinophilia: report of an extraordinary case - Agaimy, Abbas; Tögel, Lars; Stöhr, Robert; Meidenbauer, Norbert; Semrau, Sabine; Hartmann, Arndt; Mantsopoulos, Konstantinos (Virchows Archiv, 2021)
Sclerosing mucoepidermoid carcinoma with eosinophilia (SMECE) is an exceedingly rare low-grade thyroid malignancy of unknown histogenesis. NUT carcinoma is another rare, highly aggressive neoplasm with predilection for the midline, defined by recurrent NUTM1 fusions. The bromodomain family genes (BRD4 or BRD3) and rarely NSD3, ZNF532, or others are known fusion partners. We describe an extraordinary case of a 42-year-old female with a thyroid SMECE treated by thyroidectomy and neck dissection. She presented 6 months later with extensive midline recurrence encasing/compressing the trachea. Biopsy revealed poorly differentiated carcinoma with abrupt squamous differentiation, suggestive of NUT carcinoma. Immunohistochemistry confirmed expression of monoclonal NUT antibody. Targeted RNA sequencing revealed the NSD3-NUTM1 fusion in the NUT carcinoma, but not in the SMECE. This unique case highlights unusual sequential origin of two exceptionally rare entities at same anatomic site and underlines the necessity of sampling unexpectedly aggressive recurrences of otherwise indolent malignancies.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Head and neck; Midline carcinoma; NSD3; NUT carcinoma; NUTM1; Sclerosing mucoepidermoid carcinoma with eosinophilia; Thyroid gland

Papillary-cystic neoplasms of the middle ear are distinct from endolymphatic sac tumours - Taverna, Cecilia; Pollastri, Federica; Pecci, Rudi; Giannoni, Beatrice; Fattorini, Caterina; Santucci, Marco; Müller, Sarina Katrin; Stöhr, Robert; Franchi, Alessandro; Agaimy, Abbas (Histopathology, 2020)
Aims Papillary neoplasms of the middle and inner ear are rare and poorly characterised. The current World Health Organization classification divides them into two major subtypes: aggressive papillary tumours (APTs) and endolymphatic sac tumours (ELSTs). The aim of this article is to present two papillary neoplasms of the middle ear that do not fit into either the classic APT category or the classic ELST category, and compare them with three ELSTs.
CRIS-Team WoS Importer:2020-11-27

Pathologie und Molekularpathologie des Peniskarzinoms - Fiegl, August; Hartmann, Arndt; Junker, Kerstin; Mink, Jan; Stöhr, Robert (Die Pathologie, 2025)
Penile carcinoma exhibits significant geographic variation in incidence, ranking 30th globally among newly diagnosed cancers with an annual rate of 0.84 cases per 100,000 men. Particularly high incidence rates of up to 2.2 are seen in Latin America, Asia, and Africa, largely due to a high prevalence of HPV, lower circumcision rates, and inadequate hygiene standards.The 2022 WHO classification of urogenital tumors continues to differentiate penile carcinomas based on their HPV status; however, the subdivision of numerous subtypes especially of the HPV(+) carcinomas was abandoned. This article aims to present current knowledge on the carcinogenesis of HPV(+) and HPV(-) penile carcinomas and their precursor lesions as well as updates from the latest WHO classification.Approximately 50% of penile carcinomas are caused by infection with high-risk HPV subtypes, with positive p16 immunohistochemistry serving as a good surrogate marker for HPV(+) tumors. HPV(-) carcinomas frequently show TP53 mutations and are associated with a poorer prognosis.While localized penile carcinomas have a relatively good prognosis, survival rates in metastatic cases remain poor. Neither microsatellite instability nor mismatch-repair deficiency appear to play a role, but up to 62.2% of tumors express PD-L1. Currently, immune checkpoint inhibitors such as Avelumab and Ipilimumab, along with antibody-drug conjugates targeting TROP2 and Nectin‑4, are being tested in clinical trials, potentially leading to the approval of targeted therapies for metastatic penile carcinoma in the future.
EVALuna2:578181

PIK3CA mutation testing as a valuable molecular surrogate for lipomatosis of the median nerve: clinicopathological and molecular analysis of six cases - Osterloh, Justus; Agaimy, Abbas; Fried, Frederick; Stöhr, Robert; Janka, Rolf Matthias; Arkudas, Andreas; Horch, Raymund E. (Virchows Archiv, 2023)
Lipomatosis of peripheral nerves (LPN, also known as fibrolipomatous or lipofibromatous hamartoma of peripheral nerves) is a very rare, benign, intraneural, tumorous lesion that predominantly involves the median nerve but may rarely affect any peripheral nerve. Recently, PIK3CA mutations have been reported in macrodactyly, a rare condition related to LPN, and in other localized lipomatous overgrowth syndromes. In this retrospective study, we report 6 cases of FPN involving the median nerve (4 of them identified among 570 patients with carpal tunnel syndrome who underwent surgical decompression at our center from 2012 to 2022 and two seen in consultation by one of the authors). All cases were diagnosed via biopsy or resection supplemented by MRI. Patients were 4 males and 2 females aged 23 to 60 years (mean 38 years). One patient with bilateral lesions had in addition extensive angiomatosis of the paravertebral region. Histological examination showed an abnormal amount of mature fatty tissue containing disordered fibrous bands, entrapping normal-looking nerve fibers with prominent perineurial and endoneurial fibrosis. Genetic analysis using snapshot assay constructed to detect hotspots mutations in PIK3CA revealed similar PIK3CA mutations (p.H1047R; c.3140A>G) in 5/6 cases (83.3%). Our study represents a further contribution to the literature on LPN and highlights the diagnostic value of PIK3CA mutation testing as surrogate tool in equivocal cases and in those lesions without associated macrodactyly, especially as the biopsy findings of this lesion are essentially nonspecific.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Everolimus; Lipomatosis; mTOR; Neuropathy; Peripheral nerves; Sequencing

Primary pseudomyogenic haemangioendothelioma of the testis with a novel POTEI::FOSB gene fusion - Gersmann, Ann Kathrin; Haller, Florian; Behnert, Nina; Richter, Annika; Stöhr, Robert; Hartmann, Arndt; Ströbel, Philipp; Bremmer, Felix (Histopathology, 2022)
CRIS-Team Scopus Importer:2022-06-03
Keywords: POTEI::FOSB; pseudomyogenic haemangioendothelioma; testis

Proficiency testing of PIK3CA mutations in HR+/HER2-breast cancer on liquid biopsy and tissue - Vollbrecht, Claudia; Hoffmann, Inga; Lehmann, Annika; Merkelbach-Bruse, Sabine; Fassunke, Jana; Wagener-Ryczek, Svenja; Ball, Markus; Dimitrova, Lora; Hartmann, Arndt; Stöhr, Robert; Erber, Ramona; Weichert, Wilko; et al. (Virchows Archiv, 2022)
Precision oncology based on specific molecular alterations requires precise and reliable detection of therapeutic targets in order to initiate the optimal treatment. In many European countries—including Germany—assays employed for this purpose are highly diverse and not prescribed by authorities, making inter-laboratory comparison difficult. To ensure reproducible molecular diagnostic results across many laboratories and different assays, ring trials are essential and a well-established tool. Here, we describe the design and results of the ring trial for the detection of therapeutically relevant PIK3CA hotspot mutations in HR+/HER2-breast cancer tissue and liquid biopsy (LB). For PIK3CA mutation detection in tissue samples, 43 of the 54 participants (80%) provided results compliant with the reference values. Participants using NGS-based assays showed higher success rate (82%) than those employing Sanger sequencing (57%). LB testing was performed with two reference materials differing in the length of the mutated DNA fragments. Most participants used NGS-based or commercial real-time PCR assays (70%). The 167 bp fragments led to a successful PIK3CA mutation detection by only 31% of participants whereas longer fragments of 490 bp were detectable even by non-optimal assays (83%). In conclusion, the first ring trial for PIK3CA mutation detection in Germany showed that PIK3CA mutation analysis is broadly established for tissue samples and that NGS-based tests seem to be more suitable than Sanger sequencing. PIK3CA mutation detection in LB should be carried out with assays specifically designed for this purpose in order to avoid false-negative results.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Alpelisib; Breast cancer; Liquid biopsy; PIK3CA; Proficiency testing

Profiling intratumoral heterogeneity of bladder cancer subtypes at the single-cell level using machine-learning assisted histopathology. - van Rhijn, Bas W. G.; Mertens, Laura; Mayr, Roman; Bostrom, Peter; Marques, Mirari; Van Leenders, Geert; Gotz, Stefanie; Van Der Heijden, Michiel; Jewett, Michael; Real, Francisco; Stöhr, Robert; Zlotta, Alexandre; et al. (CLINICAL CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2020-08-28

Prognostic and Predictive Potential of CCL5 Expression in Muscle-Invasive Bladder Cancer Patients - Smolka, Cedric; Eckstein, Markus; Jung, Rudolf; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Bahlinger, Veronika; Bertz, Simone; Kehlen, Astrid; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (International Journal of Molecular Sciences, 2024)
Bladder cancer (BC) is the 12th most commonly diagnosed cancer worldwide. Although there are several well-established molecular and immunological classifications, prognostic and predictive markers for tumor cells and immune cells are still needed. Using a tissue microarray, we analyzed the expression of the chemokine CC motif ligand 5 (CCL5) by immunohistochemistry (IHC) in 175 muscle-invasive BC samples. The application of a single cutoff for the staining status of tumor cells (TCs; positive vs. negative) and immune cells (ICs; positive vs. negative) revealed 75 patients (42.9%) and 123 patients (70.3%) with CCL5-positive TCs or ICs, respectively. IHC results were associated with prognostic and predictive data. Multivariate Cox regression analysis revealed that positive CCL5 staining in TCs was associated with significantly shorter disease-specific survival (DSS; RR = 1.51; p = 0.047), but CCL5-negative ICs were associated with significantly shorter overall survival (OS; RR = 1.66; p = 0.005), DSS (RR = 2.02; p = 0.001) and recurrence-free survival (RFS; RR = 1.94; p = 0.002). Adjuvant chemotherapy was favorable for patients with CCL5-negative ICs for OS (RR = 0.30; p = 0.006), DSS (RR = 0.36; p = 0.022) and RFS (RR = 0.41; p = 0.046) but not for patients with CCL5-positive ICs, except in the subgroup of N1 + N2 patients, where it was associated with better OS. We suggest that CCL5 expression can be a prognostic and predictive marker for muscle-invasive bladder cancer patients.
CRIS-Team Scopus Importer:2024-07-12
Keywords: CCL5; chemokine; chemotherapy; immune cells; muscle-invasive bladder cancer; prognosis; tumor cells

Prognostic and Predictive Value of Fibroblast Growth Factor Receptor Alterations in High-grade Non–muscle-invasive Bladder Cancer Treated with and Without Bacillus Calmette-Guérin Immunotherapy - Mayr, Roman; Eckstein, Markus; Wirtz, Ralph M.; Santiago-Walker, Ademi; Baig, Mahadi; Sundaram, Ramesh; Carcione, Jenna Cody; Stöhr, Robert; Hartmann, Arndt; Bolenz, Christian; Burger, Maximilian; Otto, Wolfgang; et al. (European Urology, 2022)
Background: Limited data are available on the prognostic and predictive value of fibroblast growth factor receptor alterations (FGFRa) relative to clinical outcomes in patients with non–muscle-invasive bladder cancer (NMIBC). Objective: To determine whether FGFRa may be clinically useful in stratifying for treatment response in a real-world cohort of patients with pT1 NMIBC treated and untreated with bacillus Calmette-Guérin (BCG) instillation therapy. Design, setting, and participants: A pooled dataset of matched clinical and genomic data (1992–2015) for pT1 NMIBC patients was assessed by the Bladder Cancer Research Initiative for Drug Targets in Germany consortium. Outcome measurements and statistical analysis: Key efficacy outcomes were recurrence-free survival (RFS), progression-free survival (PFS), and disease-specific survival (DSS), which were estimated by Kaplan-Meier analysis, with hazard ratios calculated using a multivariate Cox proportional-hazard model. Results and limitations: In this retrospective study of 263 patients with high-grade NMIBC, at a median follow-up of 63 mo, 32% showed recurrence and 15% progressed to muscle-invasive bladder cancer. FGFRa were found in 43% of patients, including 39% mutations and 5.7% fusions. FGFRa were associated with lower rates of concomitant carcinoma in situ. Among patients with or without FGFRa, there was no significant difference in PFS, RFS, and DSS in those who were BCG treated or BCG naive, or in the overall population. Limitations include the retrospective design from a single-center setting. Conclusions: In patients with high-risk NMIBC, FGFRa were frequently observed. Patients with FGFRa who often exhibit recurrence/relapse after BCG treatment have a high unmet need. Patient summary: Our retrospective study suggests that fibroblast growth factor receptor alterations (FGFRa) occur frequently in non–muscle-invasive bladder cancer (NMIBC). Outcomes were similar with or without FGFRa in patients with NMIBC, both overall and for standard bacillus Calmette-Guérin (BCG) treatment.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Bacillus Calmette-Guérin; Bladder cancer; FGFR alterations; Fibroblast growth factor receptor; Non–muscle-invasive bladder cancer

Prognostic impact of molecular muscle-invasive bladder cancer subtyping approaches and correlations with variant histology in a population-based mono-institutional cystectomy cohort - Weyerer, Veronika; Stöhr, Robert; Bertz, Simone; Lange, Fabienne; Geppert, Carol-Immanuel; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (World Journal of Urology, 2021)
Purpose Recently discovered molecular classifications for urothelial bladder cancer appeared to be promising prognostic and predictive biomarkers. The present study was conducted to evaluate the prognostic impact of molecular subtypes assessed by two different methodologies (gene and protein expression), to compare these two approaches and to correlate molecular with histological subtypes in a consecutively collected, mono-institutional muscle-invasive bladder cancer (MIBC) cohort. Methods 193 MIBC were pathologically re-evaluated and molecular subtypes were assessed on mRNA (NanoString technology, modified 21-gene-containing MDACC approach) and protein levels (immuno-histochemical [IHC] analysis of CK5, CK14, CD44, CK20, GATA3 and FOXA1). Descriptive statistical methods and uni-/multi-variable survival models were employed to analyze derived data. Results Neither gene expression nor protein-based subtyping showed significant associations with disease-specific (DSS) or recurrence-free survival (RFS). Agreement between mRNA (reference) and protein-based subtyping amounted 68.6% for basal, 76.1% for luminal and 50.0% for double-negative tumors. Histological subtypes associated with RFS in uni-variable (P = 0.03), but not in multivariable survival analyses. Tumors with variant histology predominantly showed luminal subtypes (gene expression subtyping: 36/55 cases, 65.5%; protein subtyping: 44/55 cases, 80.0%). Squamous differentiation significantly associated with basal subtypes (gene expression subtyping: 44/45 squamous cases, 97.8%; protein subtyping: 36/45 cases, 80.0%). Conclusion In our consecutive cystectomy cohort, neither gene, protein expression-based subtyping, nor histological subtypes associated with DSS or RFS in multi-variably adjusted survival analyses. Application of a limited IHC subtyping marker panel showed high concordance of 83.9% with gene expression-based subtyping, thus underlining the utility for subtyping in pathological routine diagnostics. In addition, histological MIBC subtypes are strong indicators for intrinsic subtypes.
CRIS-Team WoS Importer:2021-07-23

Prognostic impact of variant histologies in urothelial bladder cancer treated with radical cystectomy - Claps, Francesco; van de Kamp, Maaike W.; Mayr, Roman; Bostrom, Peter J.; Shariat, Shahrokh F.; Hippe, Katrin; Bertz, Simone; Neuzillet, Yann; Sanders, Joyce; Otto, Wolfgang; van der Heijden, Michiel S.; Jewett, Michael A.S.; et al. (Bju International, 2023)
Objectives: To evaluate variant histologies (VHs) for disease-specific survival (DSS) in patients with invasive urothelial bladder cancer (BCa) undergoing radical cystectomy (RC). Materials and Methods: We analysed a multi-institutional cohort of 1082 patients treated with upfront RC for cT1-4aN0M0 urothelial BCa at eight centres. Univariable and multivariable Cox’ regression analyses were used to assess the effect of different VHs on DSS in overall cohort and three stage-based analyses. The stages were defined as ‘organ-confined’ (≤pT2N0), ‘locally advanced’ (pT3-4N0) and ‘node-positive’ (pTanyN1-3). Results: Overall, 784 patients (72.5%) had pure urothelial carcinoma (UC), while the remaining 298 (27.5%) harboured a VH. Squamous differentiation was the most common VH, observed in 166 patients (15.3%), followed by micropapillary (40 patients [3.7%]), sarcomatoid (29 patients [2.7%]), glandular (18 patients [1.7%]), lymphoepithelioma-like (14 patients [1.3%]), small-cell (13 patients [1.2%]), clear-cell (eight patients [0.7%]), nested (seven patients [0.6%]) and plasmacytoid VH (three patients [0.3%]). The median follow-up was 2.3 years. Overall, 534 (49.4%) disease-related deaths occurred. In uni- and multivariable analyses, plasmacytoid and small-cell VHs were associated with worse DSS in the overall cohort (both P = 0.04). In univariable analyses, sarcomatoid VH was significantly associated with worse DSS, while lymphoepithelioma-like VH had favourable DSS compared to pure UC. Clear-cell (P = 0.015) and small-cell (P = 0.011) VH were associated with worse DSS in the organ-confined and node-positive cohorts, respectively. Conclusions: More than 25% of patients harboured a VH at time of RC. Compared to pure UC, clear-cell, plasmacytoid, small-cell and sarcomatoid VHs were associated with worse DSS, while lymphoepithelioma-like VH was characterized by a DSS benefit. Accurate pathological diagnosis of VHs may ensure tailored counselling to identify patients who require more intensive management.
CRIS-Team Scopus Importer:2023-03-03
Keywords: #BladderCancer; #blcsm; #uroonc; #utuc; bladder urothelial carcinoma; prognosis; radical cystectomy; survival; variant histology

Prognostic markers in invasive bladder cancer: FGFR3 mutation status versus P53 and KI-67 expression: a multi-center, multi-laboratory analysis in 1058 radical cystectomy patients - Mertens, Laura S.; Claps, Francesco; Mayr, Roman; Bostrom, Peter J.; Shariat, Shahrokh F.; Zwarthoff, Ellen C.; Boormans, Joost L.; Abas, Cheno; van Leenders, Geert J.L.H.; Götz, Stefanie; Hippe, Katrin; Bertz, Simone; et al. (Urologic Oncology-Seminars and Original Investigations, 2022)
Objectives: To determine the association between the FGFR3 mutation status and immuno-histochemistry (IHC) markers (p53 and Ki-67) in invasive bladder cancer (BC), and to analyze their prognostic value in a multicenter, multi-laboratory radical cystectomy (RC) cohort. Patients and methods: We included 1058 cN0M0, chemotherapy-naive BC patients who underwent RC with pelvic lymph-node dissection at 8 hospitals. The specimens were reviewed by uro-pathologists. Mutations in the FGFR3 gene were examined using PCR-SNaPshot; p53 and Ki-67 expression were determined by standard IHC. FGFR3 mutation status as well as p53 (cut-off>10%) and Ki-67 (cut-off>20%) expression were correlated to clinicopathological parameters and disease specific survival (DSS). Results: pT-stage was
CRIS-Team Scopus Importer:2022-03-04
Keywords: Bladder; Cancer; Cystectomy; FGFR3; Immunohistochemistry; Ki-67; Mutation; p53; Urothelial carcinoma

Prognostic Role of FGFR Alterations and FGFR mRNA Expression in Metastatic Urothelial Cancer Undergoing Checkpoint Inhibitor Therapy - Tully, Karl H.; Jütte, Hendrik; Wirtz, Ralph M.; Jarczyk, Jonas; Santiago-Walker, Ademi; Zengerling, Friedemann; Breyer, Johannes; Sikic, Danijel; Kriegmair, Maximilian C.; von Hardenberg, Jost; Wullich, Bernd; Taubert, Helge; et al. (Urology, 2021)
Objective: To examine the disease-specific survival(DSS) after checkpoint inhibitor(CPI) therapy based on FGFR alterations and FGFR mRNA expression levels in patients with metastatic urothelial cancer(mUCa) within a multi-center cohort. Methods: Within a cohort of 72 patients with mUCa from five academic centers in Germany FGFR alterations, as well as FGFR1-4 mRNA expression levels in tumor samples from the primary tumor or metastatic sites. Spearman rank correlations, logistic regression, as well as Kaplan-Meier survival analyses and univariate Cox proportional hazards regression models were employed to examine the impact of different FGFR patterns on the DSS after CPI treatment. Results: FGFR3 mutations or gene fusions (gene alterations) were detected in 16.9% of all samples. Patients with or without FGFR3 gene alterations did not show different oncological outcomes undergoing CPI treatment. Low expression of FGFR2 mRNA alone, as well as the combination of either low FGFR2mRNA expression and FGFR3 gene alteration or high FGFR3mRNA expression (P = 0.027), identified a subgroup of patients with unfavorable outcomes, comprising 40% of the total cohort. This trend was also observed in univariate Cox proportional hazards regression analysis(FGFR3 gene alteration: Hazard ratio(HR) 5.33, 95%Confidence interval(CI)1.76-15.0, P = 0.004; FGFR3mRNA expression:HR 3.04, 95%CI 1.40-7.13, P = 0.005). Conclusion: Assessment of FGFR mRNA expression identified a high-risk subgroup of patients with mUCa. These patients showing overexpression of FGFR3 mRNA were found to have unfavorable DSS after CPI treatment. Using this approach may be suitable for identifying a patient population with poor response to CPI treatment, which may benefit from early FGFR inhibition.
CRIS-Team Scopus Importer:2021-07-30

Prognostic role of FGFR Mutations and FGFR mRNA expression in metastatic urothelial cancer treated with anti-PD(L1) inhibitors in first and second-line setting - Roghmann, F.; Wirtz, R.; Jarczyk, J.; Kriegmair, M. C.; Worst, T. S.; Sikic, D.; Wach, S.; Taubert, Helge; Wullich, Bernd; Weyerer, Veronika; Stöhr, Robert; Zengerling, F.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Progranulin (GP88) is an independent prognostic factor for prostate cancer patients - Taubert, Helge; Abdulrahman, Amer; Eckstein, Markus; Jung, Rudolf; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Yue, Binbin; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2021-03-05

Protein levels of Piwi-like 1 and-2 protein are prognostic factors for muscle invasive urothelial bladder cancer patients - Eckstein, Markus; Jung, Rudolf; Weigelt, Katrin; Sikic, Danijel; Stöhr, Robert; Geppert, Carol-Immanuel; Agaimy, Abbas; Lieb, Verena; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; Taubert, Helge (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

Pure large nested variant of urothelial carcinoma (Lnuc) is the prototype of an fgfr3 mutated aggressive urothelial carcinoma with luminal-papillary phenotype - Weyerer, Veronika; Eckstein, Markus; Compérat, Eva; Juette, Hendrik; Gaisa, Nadine T.; Allory, Yves; Stöhr, Robert; Wullich, Bernd; Rouprêt, Morgan; Hartmann, Arndt; Bertz, Simone (Cancers, 2020)
Since 2016, large nested urothelial carcinoma (LNUC) has been included within the WHO classification of urothelial tumors. Limited reports with mainly small case series have confirmed the malignant behavior of LNUC despite its bland morphological appearance. We evaluated, for the first time, markers for new immunooncological or targeted therapies including FGFR3 mutational status and PD-L1 status, the frequency of TERT-promoter mutations and the molecular subtype in a cohort of 25 LNUC using SNaPshot analysis and immunohistochemistry. Of the 25 cases, 17 were pure LNUC, with 13 showing an additional exophytic papillary/papillary-like component. Seven mixed LNUCs presented areas of classical nested variant urothelial carcinoma (NVUC) and one showed a component of conventional urothelial carcinoma. Of the 17 evaluable pure LNUCs, 16 were FGFR3-mutated with identical mutations in their concomitant papillary/papillary-like components. An FGFR3 mutation was found in 1/7 evaluable mixed LNUCs combined with NVUC. TERT-promoter mutations were detected in 86.7% pure and 83.3% mixed tumors. Immunohistochemistry revealed a luminal phenotype; PD-L1 was negative in the majority of tumor cells and tumor-associated immune cells. Pure LNUC is a prime example of a luminal, FGFR3-mutated, mostly PD-L1-negative tumor. In contrast, FGFR3 mutations seem to be rare in mixed LNUC, which may indicate a different pathway of tumor development.
CRIS-Team Scopus Importer:2020-04-14
Keywords: FGFR3 mutation; Large nested variant; LNUC; Luminal subtype; Urothelial carcinoma

Quality-Assured Analysis of PIK3CA Mutations in Hormone Receptor–Positive/Human Epidermal Growth Factor Receptor 2–Negative Breast Cancer Tissue: A Story About the Need for Proficiency Testing for High-Quality Molecular Biomarker Reporting in Precision Medicine - Schmidt, Carolin; Stöhr, Robert; Dimitrova, Lora; Beckmann, Matthias; Rübner, Matthias; Fasching, Peter; Denkert, Carsten; Lehmann, Ulrich; Vollbrecht, Claudia; Haller, Florian; Hartmann, Arndt; Erber, Ramona (Journal of Molecular Diagnostics, 2024)
In precision oncology, reliable testing of predictive molecular biomarkers is a prerequisite for optimal patient treatment. Interlaboratory comparisons are a crucial tool to verify diagnostic performance and reproducibility of one's approach. Herein is described the design and results of the first recurrent, internationally performed PIK3CA (phosphatidylinositol-4,5-bisphosphate 3 kinase catalytic subunit α) breast cancer tissue external quality assessment (EQA), organized by German Quality in Pathology GmbH and started in 2021. After the internal pretesting phase performed by the (lead) panel institutes, in both 2021 and 2022, each EQA test set comprised n = 10 tissue samples of hormone receptor–positive, human epidermal growth factor receptor 2–negative invasive breast cancer that had to be analyzed and reported by the participants. In 2021, the results were evaluated separately for German-speaking countries (part 1) and international laboratories (part 2). In 2022, the EQA was performed across the European Union. The EQA success rates were 84.6% (n = 11/13), 88.6% (n = 39/44), and 87.9% (n = 29/33) for EQA 2021 part 1, part 2, and EQA 2022, respectively. The most commonly used methods were next-generation sequencing and mutation-/allele-specific qualitative PCR-based assays. In summary, this recurrent PIK3CA EQA proved to be a suitable approach to obtain an international overview of methods used for PIK3CA mutation analysis, to evaluate them qualitatively, and identify the strengths and weaknesses of individual methods.
CRIS-Team Scopus Importer:2024-05-31

Rapidly fatal SMARCA4-deficient undifferentiated sarcoma originating from hybrid hemosiderotic fibrolipomatous tumor/pleomorphic hyalinizing angiectatic tumor of the foot - Agaimy, Abbas; Meidenbauer, Norbert; Sukov, William R.; Stöhr, Robert; Vieth, Michael; Roemer, Frank; Grützmann, Robert; Folpe, Andrew L. (Virchows Archiv, 2021)
Pleomorphic hyalinizing angiectatic tumor (PHAT) of soft parts and hemosiderotic fibrolipomatous tumor (HFLT) are two rare low-grade locally recurring neoplasms with predilection for the foot/ankle. Recent studies support a close link between the two entities, and origin of PHAT from HFLT and occurrence of hybrid HFLT/PHAT have been documented. Both lesions often harbor TGFBR3 or MGEA5 rearrangements. Rare sarcomas originating from HFLT/PHAT have been reported, typically resembling myxofibrosarcoma or myxoinflammatory fibroblastic sarcoma. We describe a novel SMARCA4-deficient undifferentiated sarcoma with rhabdoid features originating from hybrid HFLT/PHAT in the foot of a 54-year-old male. The tumor pursued a highly aggressive course with rapid regrowth after resection and multiple metastases resulting in patient's death within 5 months, despite systemic chemotherapy. Immunohistochemistry revealed SMARCA4 loss in the undifferentiated sarcoma, but not in the HFLT/PHAT. Molecular testing confirmed TGFBR3/MGEA5 rearrangements. This report expands the phenotypes of sarcomas developing from pre-existing PHAT/HFLT.
CRIS-Team WoS Importer:2021-08-27

Recurrent EWSR1::COLCA2 Fusions Define a Novel Sarcoma With Spindle/Round Cell Morphology and Strong Predilection for the Sinonasal Tract. - Agaimy, Abbas; Baněčková, Martina; De Almeida, John; Dickson, Brendan C.; Dimmler, Arno; Hartmann, Wolfgang; Laé, Marick; Pablik, Jessica; Schubart, Christoph; Skálová, Alena; Stöhr, Robert; Trautmann, Marcel; et al. (American Journal of Surgical Pathology, 2023)
The last 2 decades have attended a dynamic evolution in the nosology of poorly differentiated sinonasal tract malignancies, with several new molecularly defined entities having been described in addition to delineation of the genetic driver/s of some established older entities. These discoveries, however, mostly concerned epithelial-derived neoplasms (carcinomas). Adamantinoma-like Ewing sarcoma and biphenotypic sinonasal sarcoma are the major representatives of the newly defined mesenchymal categories. The colorectal cancer associated 2 (COLCA2) has been discovered recently as a colorectal cancer risk gene locus, but fusions involving this gene have not been well characterized. We, herein, describe clinicopathologic and molecular features of a novel sinonasal sarcoma characterized by undifferentiated spindle/round cell morphology and defined by recurrent EWSR1::COLCA2 fusions. All patients (n=5) were adults (3 female and 2 male) with a median age of 46 years (range, 23 to 60 y). The tumors originated in different subsites of the sinonasal tract with frequent multisite involvement. Original diagnoses were undifferentiated or unclassified round cell/spindle cell neoplasm/sarcoma (n=4) and neuroendocrine carcinoma (n=1). Surgery with or without adjuvant chemoradiation was the treatment in all cases. At the last follow-up, 1 patient developed multiple local recurrences over 21 years and another developed local recurrence and distant metastasis to bone 27 months after diagnosis. A third patient developed local recurrence 11 months later. Two patients were disease-free at 23, and 24 months. Histology showed nondescript highly cellular neoplasms with an admixture of spindled and round cells disposed into solid sheets and fascicles with brisk mitotic activity. Immunohistochemistry was negative for all lineage-specific markers with only limited focal membranous CD99 (4 of 5 cases) and weak pankeratin (1 of 5 cases) expression. Targeted RNA sequencing revealed an EWSR1::COLCA2 fusion, verified by EWSR1 fluorescence in situ hybridization, in all cases. This series identifies a novel member in the undifferentiated spindle/round cell sarcoma category with strong predilection for the sinonasal tract. None of >10,000 epithelial and mesenchymal neoplasms tested at the authors' centers during the same period showed this fusion, highlighting rarity of tumors carrying this gene fusion. Accordingly, molecular testing of unclassified sinonasal malignancies/sarcomas showing round and spindle cell morphology is recommended to enhance the identification and further characterization of this entity.
EVALuna2:518253

Recurrent IDH2 Mutations in Salivary Gland Striated Duct Adenoma Define an Expanded Histologic Spectrum Distinct From Canalicular Adenoma - Rooper, Lisa M.; Agaimy, Abbas; Assaad, Adel; Bal, Munita; Eugene, Henrietta; Gagan, Jeffrey; Nonogaki, Hiro; Palsgrove, Doreen N.; Shah, Akeesha; Stelow, Edward; Stöhr, Robert; Thompson, Lester D. R.; et al. (American Journal of Surgical Pathology, 2023)
Striated duct adenoma (SDA) is a rare salivary gland neoplasm defined by histologic similarity to normal striated ducts. However, doubt persists about whether SDA represents a genuine entity distinct from canalicular adenoma and if a malignant counterpart exists. This study aims to evaluate the molecular underpinnings of SDA to clarify its pathogenesis and classification. We identified 10 SDA and 2 tumors called low-grade adenocarcinoma not otherwise specified that were retrospectively recognized to resemble SDA. All cases showed recurrent histologic features including (1) discrete monophasic tubules, (2) tall columnar eosinophilic cells, (3) monotonous oval nuclei, and (4) scant fibrous stroma, and most were positive for S100 protein (91%), SOX10 (80%), and CK7 (80%). Although 1 case was previously called adenocarcinoma based on interdigitation with normal acini, this pattern was also seen in some SDA, and likely does not indicate malignancy; the significance of growth surrounding nerve in 1 other case is less clear. Targeted sequencing identified IDH2 R172X mutations in all 8 cases with sufficient tissue, with positivity for IDH1/2 mutation-specific immunohistochemistry in 9 cases stained. In contrast, 5 canalicular adenomas lacked IDH2 mutations or other oncogenic alterations. Overall, IDH2 R172X mutations are a defining feature of SDA that, in combination with its recognizable pathologic profile, confirm it is a unique entity separate from canalicular adenoma. IDH1/2 mutation-specific immunohistochemistry may provide a convenient tool to facilitate diagnosis. Both morphology and IDH2 mutations raise parallels between SDA and breast tall cell carcinoma with reverse polarity.
CRIS-Team WoS Importer:2023-03-17

Recurrent KAT6B/A::KANSL1 Fusions Characterize a Potentially Aggressive Uterine Sarcoma Morphologically Overlapping With Low-grade Endometrial Stromal Sarcoma. - Agaimy, Abbas; Clarke, Blaise A.; Kolin, David L.; Lee, Cheng-Han; Lee, Jen-Chieh; Mccluggage, W. Glenn; Pöschke, Patrik; Stöhr, Robert; Swanson, David; Turashvili, Gulisa; Beckmann, Matthias; Hartmann, Arndt; et al. (American Journal of Surgical Pathology, 2022)
With the widespread application of next-generation sequencing, the genetic landscape of uterine mesenchymal neoplasms has been evolving rapidly to include several recently identified fusion genes. Although chromosomal rearrangements involving the 10q22 and 17q21.31 loci have been reported in occasional uterine leiomyomas decades ago, the corresponding KAT6B::KANSL1 fusion has been only recently identified in 2 uterine tumors diagnosed as leiomyoma and leiomyosarcoma. We herein describe 13 uterine stromal neoplasms carrying a KAT6B::KANSL1 (n=11) and KAT6A::KANSL1 (n=2) fusion. Patient ages ranged from 33 to 81 years (median, 49 y). Tumor size was 2.6 to 23.5 cm (median, 8.2 cm). Nine tumors were myometrium-centered, and 3 had an intracavitary component. Original diagnoses were mostly low-grade endometrial stromal sarcoma (LG-ESS; 10 cases) with atypical features (limited CD10 expression, sex cord-like features, pericytic vasculature, and frequent myxoid changes). Treatment was hysterectomy±bilateral salpingo-oophorectomy (10), myomectomy (1), and curettage (2). Five patients were disease-free at 6 to 34 months, 3 (27%) died of disease at 2 to 47 months, and 3 were alive with disease at 2, 17, and 17 years. Histologically, most tumors showed variable overlap with LG-ESS, but they were generally well-circumscribed lacking the extensive permeative and angioinvasive growth typical of LG-ESS. They were composed of monotonous medium-sized oval and spindle cells arranged into diffuse sheets with prominent spiral-type arterioles and frequent pericytoma-like vascular pattern. Variable myxoid stromal changes were frequent. Mitotic activity ranged from 1 to >20 in 10 HPFs. Immunohistochemistry showed variable expression of CD10 (12/13), estrogen receptor (8/11), progesterone receptor (8/11), smooth muscle actin (9/11), desmin (4/12), h-caldesmon (2/10), calretinin (3/8), inhibin (1/7), WT1 (4/7), cyclin D1 (5/11; diffuse in only 1 case), and pankeratin (5/10). This series characterizes a KAT6B/A::KANSL1 fusion-positive uterine stromal neoplasm within the morphologic spectrum of LG-ESS but with atypical features. The relationship of these neoplasms to genuine LG-ESS remains unclear. This molecular subtype of uterine endometrial stromal sarcoma has the potential for an unfavorable clinical course despite the absence of widely invasive growth; nevertheless, analysis of more cases is necessary to delineate the phenotypic spectrum and biological potential of this tumor.
EVALuna2:504168

Recurrent VGLL3 fusions define a distinctive subset of spindle cell rhabdomyosarcoma with an indolent clinical course and striking predilection for the head and neck - Agaimy, Abbas; Dermawan, Josephine K.; Leong, Iona; Stöhr, Robert; Swanson, David; Weinreb, Ilan; Zhang, Lingxin; Antonescu, Cristina R.; Dickson, Brendan C. (Genes Chromosomes & Cancer, 2022)
The mammalian Vestigial-like (VGLL) transcriptional cofactor family of proteins VGLL1-4 has recently emerged as an important player in the tumorigenesis of diverse neoplasms. The role of VGLL3 in soft tissue tumors is exemplified by its amplification in myxoinflammatory fibroblastic sarcoma and its rearrangement (fused to CHD7, CHD9, or MAMLD1) in hybrid schwannoma-perineurioma. This study characterizes a distinctive low-grade myogenic neoplasm with a striking predilection for the head and neck, characterized by VGLL3 fusions. The study includes five males and one female patient, aged 30–71 years (median, 56). Three tumors originated in the tongue, with one case each in the nasopharynx, oral cavity, and oropharynx. The VGLL3 fusion partners included TCF12 (n = 3), EP300 (n = 2), and PPARGC1A (n = 1). The tumor size range was 0.8–1.6 cm (all, but one, was <1 cm). Histologically, all tumors displayed bland spindle to ovoid cells arranged into vague fascicular and diffuse patterns. Mitotic activity ranged from 1 to 7 per 10 HPFs. Five tumors were muscle-centered and infiltrative, and one was centered beneath nasopharyngeal mucosa. Immunohistochemistry revealed consistent expression of desmin (diffuse in four and patchy in two cases) associated with patchy smooth muscle actin expression (4/6), and focal reactivity for myogenin (5/6) and myoD1 (1/3). All patients were managed surgically; one patient each received adjuvant radio- or chemotherapy. Three patients with follow-up were without disease at 8, 19, and 60 months and one was alive with unknown disease status at 24 months. All VGLL3 fusions were in-frame and involved exon 2, fused with either TCF12 exon 16, EP300 exon 31, or PPARGC1A exon 5, respectively. This series characterizes a distinctive subset of spindle cell rhabdomyosarcoma (RMS) with a predilection for the head and neck in adults, defined by VGLL3 fusions, likely indolent behavior and limited rhabdomyoblastic differentiation. Further delineation of this entity and differentiation from more aggressive molecular subtypes of spindle cell RMS is mandatory to define the most appropriate therapeutic strategy and avoid overtreatment.
CRIS-Team Scopus Importer:2022-08-12
Keywords: EP300; gene fusion; head and neck; PPARGC1A; sarcoma; spindle cell rhabdomyosarcoma; TCF12; VGLL3

Recurrent Wnt Pathway and ARID1A Alterations in Sinonasal Olfactory Carcinoma - Rooper, Lisa M.; Agaimy, Abbas; Bell, Diana; Gagan, Jeffrey; Gallia, Gary L.; Jo, Vickie Y.; Lewis, James S.; London, Nyall R.; Nishino, Michiya; Stöhr, Robert; Thompson, Lester D.R.; Din, Nasir Ud; et al. (Modern Pathology, 2024)
Sinonasal tumors with neuroepithelial differentiation, defined by neuroectodermal elements reminiscent of olfactory neuroblastoma (ONB) and epithelial features such as keratin expression or gland formation, are a diagnostically challenging group that has never been formally included in sinonasal tumor classifications. Recently, we documented that most of these neuroepithelial neoplasms have distinctive histologic and immunohistochemical findings and proposed the term “olfactory carcinoma” to describe these tumors. However, the molecular characteristics of olfactory carcinoma have not yet been evaluated. In this study, we performed targeted molecular profiling of 23 sinonasal olfactory carcinomas to further clarify their pathogenesis and classification. All tumors included in this study were composed of high-grade neuroectodermal cells that were positive for pankeratin and at least 1 specific neuroendocrine marker. A significant subset of cases also displayed rosettes and neurofibrillary matrix, intermixed glands with variable cilia, peripheral p63/p40 expression, and S100 protein-positive sustentacular cells. Recurrent oncogenic molecular alterations were identified in 20 tumors, including Wnt pathway alterations affecting CTNNB1 (n = 8) and PPP2R1A (n = 2), ARID1A inactivation (n = 5), RUNX1 mutations (n = 3), and IDH2 hotspot mutations (n = 2). Overall, these findings do demonstrate the presence of recurrent molecular alterations in olfactory carcinoma, although this group of tumors does not appear to be defined by any single mutation. Minimal overlap with alterations previously reported in ONB also adds to histologic and immunohistochemical separation between ONB and olfactory carcinoma. Conversely, these molecular findings enhance the overlap between olfactory carcinoma and sinonasal neuroendocrine carcinomas. A small subset of neuroepithelial tumors might better fit into the superseding molecular category of IDH2-mutant sinonasal carcinoma. At this point, sinonasal neuroendocrine and neuroepithelial tumors may best be regarded as a histologic and molecular spectrum that includes core groups of ONB, olfactory carcinoma, neuroendocrine carcinoma, and IDH2-mutant sinonasal carcinoma.
CRIS-Team Scopus Importer:2024-03-29
Keywords: adenocarcinoma; immunohistochemistry; molecular diagnostics; nasal neoplasms; neuroendocrine carcinoma; olfactory carcinoma; olfactory neuroblastoma; teratocarcinosarcoma

Recurrent YAP1-TFE3 Gene Fusions in Clear Cell Stromal Tumor of the Lung - Agaimy, Abbas; Stöhr, Robert; Michal, Michael; Christopoulos, Petros; Winter, Hauke; Zhang, Lei; Stenzinger, Albrecht; Michal, Michal; Mechtersheimer, Gunhild; Antonescu, Cristina R. (American Journal of Surgical Pathology, 2021)
Clear cell (hemangioblastoma-like) stromal tumor of the lung (CCST-L) is a recently described distinctive rare pulmonary neoplasm of unknown histogenesis and molecular pathogenesis. Only 7 cases have been reported in 2 recent studies, although additional cases might have been reported under the heading of extraneural pulmonary hemangioblastoma. We herein describe 4 CCST-L cases, 3 of them harboring a YAP1-TFE3 fusion. The fusion-positive tumors occurred in 3 women, aged 29, 56, and 69 years. All presented with solitary lung nodules measuring 2.3 to 9.5 cm. Histologically, all tumors showed similar features being composed of relatively uniform medium-sized epithelioid to ovoid cells with clear cytoplasm and small round monomorphic nuclei. Scattered larger cells with enlarged hyperchromatic nuclei and marked pleomorphism were noted in 2 cases. The tumors were associated with a hypervascularized stroma with variable but essentially subtle resemblance to capillary hemangioblastoma and perivascular epithelioid cell tumor (PEComa). Immunohistochemistry was negative for all lineage-specific markers. Targeted RNA sequencing showed a YAP1-TFE3 fusion in 3 of 4 cases. All 3 tumors showed homogeneous nuclear TFE3 immunoreactivity. Two patients were disease free at 36 and 12 months. The third patient had biopsy-proven synchronous renal and hepatic metastases, but extended follow-up is not available (recent case). The fourth case lacking the fusion affected a 66-year-old woman and showed subtle histologic differences from the fusion-positive cases, but had comparable TFE3 immunoreactivity. CCST-L represents a distinctive entity unrelated to hemangioblastoma and likely driven by recurrent YAP1-TFE3 fusions in most cases. The relationship of our cases to the recently reported "hemangioblastoma-like" CCST-L remains to be determined. Analysis of larger series is paramount to delineate the morphologic spectrum and biological behavior of this poorly characterized entity.
CRIS-Team WoS Importer:2021-10-29

Regulation of uptake of 18F-FDG by a follicular human thyroid cancer cell line with mutation-activated K-ras - Prante, Olaf; Maschauer, Simone; Fremont, Valerie; Reinfelder, Julia; Stöhr, Robert; Szkudlinski, Mariusz; Weintraub, Bruce; Hartmann, Arndt; Kuwert, Torsten (Journal of Nuclear Medicine, 2009)

Reproducibility of mRNA-Based Testing of ESR1, PGR, ERBB2, and MKI67 Expression in Invasive Breast Cancer-A Europe-Wide External Quality Assessment - Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Rübner, Matthias; Stöhr, Robert; Beckmann, Matthias; Zentgraf, Miriam; Popp, Verena; Weidler, Jodi; Simon, Iris; Becker, Steffi; Hübner, Hanna; et al. (Cancers, 2021)
Simple Summary Four biomarkers [estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2], are used to stratify breast cancer (BC) into subtypes predictive of therapy response. In a Europe-wide external quality assessment, we compared performance of an mRNA-based method [Xpert(R) Breast Cancer STRAT4 (CE-IVD)] for determining ESR1, PGR, ERBB2, and MKI67 expression against the gold standard [immunohistochemistry (IHC)/HER2 in situ hybridization (ISH)]. The coordinating center (CC) and five European laboratories tested ten breast cancer samples. STRAT4 binary (positive or negative) results of each marker were compared with the gold standard. ESR1 and ERBB2 mRNA results were concordant with IHC/ISH in all single analyses. In contrast, PGR and MKI67 results were discordant in a few cases, which had STRAT4 expression values close to assay cut-offs and immunohistochemically presented heterogeneous low positive PgR and heterogeneous Ki-67. STRAT4 assay may be a reproducible method. However, cases with expression values close to cut-offs should be carefully reviewed. Estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2 immunohistochemistry (IHC) together with HER2 in situ hybridization (ISH) are utilized to classify invasive breast cancer (IBC) into predictive molecular subtypes. As IHC evaluation may be hampered by analytical errors, gene expression assays could offer a reliable alternative. In this first Europe-wide external quality assessment (EQA) study, we investigated performance of mRNA-based Xpert(R) Breast Cancer STRAT4 (CE-IVD) in five European laboratories. The cohort comprised ten pre-therapy IBC core biopsies diagnosed in the coordinating center (CC). STRAT4 binary (positive or negative) mRNA results of each marker (ESR1, PGR, ERBB2, MKI67) were compared with the gold standard IHC/ISH performed by the CC. Sensitivity, specificity, and accuracy of ESR1 and ERBB2 mRNA were 100% for all samples. In contrast, PGR expression was falsely negative for one case by two sites and MKI67 falsely negative for two cases (respectively by four and one sites). These cases had STRAT4 expression values close to assay cut-offs and immunohistochemically presented heterogeneous low positive PgR and heterogeneous Ki-67. Our EQA shows that STRAT4 mRNA assay may be a reproducible method to evaluate ER, PgR, HER2, and Ki-67 status. However, cases with expression values close to assay cut-offs should be carefully reviewed.
CRIS-Team WoS Importer:2021-10-08

Risk of penile tumor development in Caucasian individuals is independent of the coding variant rs7208422 in the TMC8 (EVER2) gene - Stöhr, Robert; Wendler, Olaf Dietrich; Giedl, Josef; Richter, Georg; Campean, Valentina; Burger, Maximilian; Bertz, Simone; Hartmann, Arndt; Gaisa, Nadine T.; Wullich, Bernd (Molecular and Clinical Oncology, 2021)
Genetic variation in the transmembrane channel-like (TMC)6/TMC8 region has been linked to beta-type human papillomavirus (HPV) infection and squamous cell carcinoma (SCC) of the skin and the head and neck, alpha-type HPV persistence and progression to cervical cancer. The functional variant rs7208422 of the TMC8 gene was suggested to have a high impact on susceptibility to beta-papillomaviruses and their oncogenic potential and to also have an influence on alpha-type HPV-related disease. The aim of the present study was to evaluate a possible influence of rs7208422 on penile cancer risk, a known alpha-type HPV-related malignancy. Therefore, the distribution of rs7208422 was determined by direct Sanger sequencing of 104 Caucasian penile SCC cases and compared to data of 3,810 controls taken from the literature. HPV detection was performed by usage of GP5+/6+ primers and subtype-specific PCR. It was observed that the distribution of rs7208422 followed the Hardy Weinberg equilibrium in both cases and controls. HPV DNA was detected in 39% of the penile SCC cases. Overall, there was no significant difference in the distribution of rs7208422 neither between cases and controls (P=0.726) nor between HPV-positive and-negative penile SCC cases (P=0.747). There was also no association between rs7208422 genotypes and age of disease onset (P=0.740). In conclusion, the present data argue against a significant impact of rs7208422 on the risk for the development of penile SCC in Caucasians. Even in combination with the HPV status, the SNP appears not to influence the risk of penile SCC in HPV-positive cases.
CRIS-Team WoS Importer:2021-11-26

RREB1::MRTFB fusion-positive extra-glossal mesenchymal neoplasms: A series of five cases expanding their anatomic distribution and highlighting significant morphological and phenotypic diversity - Agaimy, Abbas; Din, Nasir Ud; Dermawan, Josephine K.; Haller, Florian; Melzer, Katja; Denz, Axel; Baumhoer, Daniel; Stöhr, Robert; Grützmann, Robert; Antonescu, Cristina R. (Genes Chromosomes & Cancer, 2022)
The RREB1::MRTFB (former RREB1::MKL2) fusion characterizes ectomesenchymal chondromyxoid tumors (EMCMT) of the tongue. Only five molecularly confirmed extra-glossal EMCMT cases have been reported recently; all occurring at head and neck or mediastinal sites. We herein describe five new cases including the first two extracranial/extrathoracic cases. The tumors occurred in three male and two female patients with an age ranging from 18 to 61 years (median, 28). Three tumors were located in the head and neck (jaw, parapharyngeal space, and nasopharyngeal wall) and two in the soft tissue (inguinal and presacral). The tumor size ranged from 3.3 to 20 cm (median, 7). Treatment was surgical without adjuvant treatment in all cases. Two cases were disease-free at 5 and 17 months; other cases were lost to follow-up. Histologically, the soft tissue cases shared a predominant fibromyxoid appearance, but with variable cytoarchitectural pattern (cellular perineurioma-like whorls and storiform pattern in one case and large polygonal granular cells embedded within a chondromyxoid stroma in the other). Two tumors (inguinal and parapharyngeal) showed spindled to ovoid and round cells with a moderately to highly cellular nondescript pattern. One sinonasal tumor closely mimicked nasal chondromesenchymal hamartoma (NCMH). Mitotic activity was low (0-5 mitoses/10 hpfs). Immunohistochemical findings were heterogeneous with variable expression of S100 (2/5), EMA (2/3), CD34 (1/4), desmin (1/4), and GFAP (1/3). Targeted RNA sequencing revealed the same RREB1::MRTFB fusion in all cases, with exon 8 of RREB1 being fused to exon 11 of MRTFB. This study expands the topographic spectrum of RREB1::MRTFB fusion-positive mesenchymal neoplasms, highlighting a significant morphological and phenotypic diversity. Overall, RREB1::MRTFB-rearranged neoplasms seem to fall into two subcategories: tumors with lobulated, chondroid, or myxochondroid epithelioid morphology (Cases 2 and 3) and those with more undifferentiated hypercellular spindle cell phenotype (Cases 1, 4, and 5). Involvement of extracranial/extrathoracic sites and the NCMH-like pattern are novel. The biology of these likely indolent or benign tumors remains to be verified in the future.
CRIS-Team WoS Importer:2022-07-29

Salivary carcinosarcoma: insight into multistep pathogenesis indicates uniform origin as sarcomatoid variant of carcinoma ex pleomorphic adenoma with frequent heterologous elements - Ihrler, Stephan; Stiefel, David; Jurmeister, Philipp; Sandison, Ann; Chaston, Nicola; Laco, Jan; Zidar, Nina; Brcic, Luka; Stöhr, Robert; Agaimy, Abbas (Histopathology, 2022)
Aims: The formal pathogenesis of salivary carcinosarcoma (SCS) remained unclear, both with respect to the hypothetical development from either preexisting pleomorphic adenoma (PA) or de novo and the clonal relationship between highly heterogeneous carcinomatous and sarcomatous components. Methods and results: We performed clinicopathological and molecular (targeted RNA sequencing) analyses on a large series of 16 cases and combined this with a comprehensive literature search (111 cases). Extensive sampling (average 11.6 blocks), combined with immunohistochemistry and molecular studies (PA-specific translocations including PLAG1 or HMGA2 proven in 6/16 cases), enabled the morphogenetic identification of PA in 15/16 cases (93.8%), by far surpassing a reported rate of 49.6%. Furthermore, we demonstrated a multistep (intraductal/intracapsular/extracapsular) adenoma-carcinoma-sarcoma-progression, based on two alternative histogenetic pathways (intraductal, 56.3%, versus myoepithelial pathway, 37.5%). Thereby, early intracapsular stages are identical to conventional carcinoma ex PA, while later extracapsular stages are dominated by secondary, frequently heterologous sarcomatous transformation with often large tumour size (>60 mm). Conclusion: Our findings strongly indicate that SCS (almost) always develops from PA, with a complex multistep adenoma-carcinoma-sarcoma-sequence, based on two alternative histogenetic pathways. The findings from this novel approach strongly suggest that SCS pathogenetically is a rare (3–6%), unique, and aggressive variant of carcinoma ex PA with secondary sarcomatous overgrowth. In analogy to changes of terminology in other organs, the term “sarcomatoid carcinoma ex PA with/without heterologous elements” might be more appropriate.
CRIS-Team Scopus Importer:2022-12-16
Keywords: carcinosarcoma; gene fusion; HMGA2; molecular testing; PLAG1; pleomorphic adenoma; salivary glands; true malignant mixed tumour

Small cell neuroendocrine carcinoma and poorly differentiated rhabdomyosarcomas of the urinary bladder in adults—A comparative analysis in favor of a common histogenesis - Bahlinger, Veronika; Stöhr, Robert; Hartmann, Arndt; Hes, Ondřej; Agaimy, Abbas (Virchows Archiv, 2024)
Rhabdomyosarcoma (RMS) of the urinary bladder in adults and elderly is an exceptionally rare neoplasm that displays poorly differentiated solid (alveolar-like) small cell pattern, frequently indistinguishable from small cell neuroendocrine carcinoma (SCNEC). However, the histogenesis of RMS and SCNEC and their inter-relationship have not been well studied and remained controversial. We herein analyzed 23 SCNEC and 3 small round cell RMS of the bladder for neuroendocrine (synaptophysin + chromogranin A) and myogenic (desmin + myogenin) marker expression and for TERT promoter mutations. In addition, the RMS cohort and one SCNEC that was revised to RMS were tested for gene fusions using targeted RNA sequencing (TruSight Illumina Panel which includes FOXO1 and most of RMS-related other genes). Overall, significant expression of myogenin and desmin was observed in one of 23 original SCNEC justifying a revised diagnosis to RMS. On the other hand, diffuse expression of synaptophysin was noted in 2 of the 4 RMS, but chromogranin A was not expressed in 3 RMS tested. TERT promoter mutations were detected in 15 of 22 (68%) SCNEC and in two of three (67%) assessable RMS cases, respectively. None of the four RMS cases had gene fusions. Our data highlights phenotypic and genetic overlap between SCNEC and RMS of the urinary bladder. High frequency of TERT promoter mutations in SCNEC is in line with their presumable urothelial origin. In addition, the presence of TERT promoter mutation in 2 of 3 RMS and lack of FOXO1 and other gene fusions in all 4 RMSs suggest a mucosal (urothelial) origin, probably representing extensive monomorphic rhabdomyoblastic transdifferentiation in SCNEC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: FOXO1 gene fusions; Rhabdomyosarcoma; Small cell neuroendocrine carcinoma; TERT promoter mutations; Urinary bladder

Status der Verfügbarkeit und Anwendung von „next generation sequencing“ (NGS) beim Harnblasenkarzinom – eine Umfrage in der Arbeitsgemeinschaft Uropathologie - Ortiz-Brüchle, N.; Muders, M.; Toma, M.; Esposito, I.; Hartmann, Arndt; Stöhr, Robert; Reis, H.; Wild, P.; Köllermann, J.; Bremmer, F.; Leichsenring, J.; Stenzinger, A.; et al. (Urologe, 2019)
Background: Technical advancement and availability of high-throughput analysis has advanced molecular subtyping of most cancers. Thus, new possibilities for precision oncology have emerged. Aim: Therefore, we aimed to collect data regarding availability and use of next generation sequencing (NGS) for urothelial cancer within the uropathology working group of the German Society of Pathology. Methods: We collected data by questionnaires and additionally asked for sequencing results of bladder cancers in the participating institutions. Results: A total of 13 university-affiliated institutes of pathology took part in the survey. All university institutes offer NGS-based molecular panel diagnostics and provide panels covering between 15 and 170 genes. Altogether, only 20 bladder cancers were sequenced in routine diagnostics and for 10 cancers potential targeted treatment options were available. Discussion: So far, despite availability of NGS diagnostics at university institutes of pathology, only few bladder cancer samples have been sequenced. Based on current data from the molecular subtyping of bladder cancers, we recommend a step-by-step protocol with basic immunohistochemistry analysis and subsequent subtype-dependent analyses, e.g., alterations of the fibroblast growth factor receptors (FGFR) or comprehensive gene panel analyses.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Bladder cancer; Molecular pathology; Next generation sequencing; Precision oncology; Targeted treatment

TERT promoter mutation analysis as a surrogate to morphology and immunohistochemistry in problematic spindle cell lesions of the urinary bladder - Bertz, Simone; Stöhr, Robert; Gaisa, Nadine T.; Wullich, Bernd; Hartmann, Arndt; Agaimy, Abbas (Histopathology, 2020)
Aims: Pseudosarcomatous myofibroblastic proliferations (PSMPs) of the urinary bladder are diagnostically challenging. Diagnostic difficulties are mainly due to frequent cytokeratin expression, variable ALK expression and worrisome morphological features suggestive of malignancy. Conversely, sarcomatoid urothelial carcinoma (UC) may show bland inflammatory myofibroblastic tumour (IMT)-like morphology. TERT promoter mutations are characteristic events in urothelial cancers, but have not been studied in PSMPs. Methods and results: We compared histomorphological and immunohistochemical features and TERT promoter status in 16 PSMPs and 18 sarcomatoid UC. In a subset of PSMPs, RNA sequencing was performed. At least focal IMT-like morphology was seen in nine of 17 sarcomatoid UC. Atypical mitoses, differentiated urothelial component and heterologous elements were the most reliable distinguishing histomorphological features of sarcomatoid UC, if present. A panel of immunohistochemistry (IHC) including ALK (clone D5F3), p53 pattern, p63 and GATA3 reliably distinguished PSMP from sarcomatoid UC. GATA3 (P = 0.001) and p53 patterns (mutant versus wild-type; P < 0.001) were differentially expressed between PSMPs and sarcomatoid UC. Diffuse pancytokeratin staining was significantly associated with PSMPs (10 of 13) compared to four of 14 sarcomatoid UCs (P = 0.012). TERT promoter mutations were found in 17 of 18 sarcomatoid UC versus none of 16 PSMPs (P < 0.001). RNA sequencing revealed ALK genetic rearrangements in one of two ALK-positive and one of 10 ALK-negative PSMPs, which revealed a novel FN1/RET gene fusion. Conclusion: Careful histomorphological analysis and differential IHC reliably distinguish the majority of PSMPs and sarcomatoid UC. In equivocal cases, TERT promoter mutation analysis and/or detection of ALK expression/rearrangements are valuable additional diagnostic adjuncts, strongly supporting sarcomatoid UC and PSMP, respectively.
CRIS-Team Scopus Importer:2020-10-02
Keywords: ALK gene rearrangement; inflammatory myofibroblastic tumour; pseudosarcomatous myofibroblastic proliferation; sarcomatoid urothelial carcinoma; TERT promoter mutation

Tert promoter mutation analysis of whole-organ mapping bladder cancers - Weyerer, Veronika; Eckstein, Markus; Strissel, Pamela; Wullweber, Adrian; Lange, Fabienne; Tögel, Lars; Geppert, Carol-Immanuel; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; et al. (Genes, 2021)
Background: Multifocal occurrence is a main characteristic of urothelial bladder cancer (UBC). Whether urothelial transformation is caused by monoclonal events within the urothelium, or by polyclonal unrelated events resulting in several tumor clones is still under debate. TERT promoter mutations are the most common somatic alteration identified in UBC. In this study, we analyzed different histological tissues from whole-organ mapping bladder cancer specimens to reveal TERT mutational status, as well as to discern how tumors develop. Methods: Up to 23 tissues from nine whole-organ mapping bladder tumor specimens, were tested for TERT promoter mutations including tumor associated normal urothelium, non-invasive urothelial lesions (hyperplasia, dys-plasia, metaplasia), carcinoma in situ (CIS) and different areas of muscle invasive bladder cancers (MIBC). The mutational DNA hotspot region within the TERT promoter was analyzed by SNaPshot analysis including three hot spot regions (−57, −124 or −146). Telomere length was measured by the Relative Human Telomere Length Quantification qPCR Assay Kit. Results: TERT promoter mutations were identified in tumor associated normal urothelium as well as non-invasive urothelial lesions, CIS and MIBC. Analysis of separate regions of the MIBC showed 100% concordance of TERT promoter mutations within a respective whole-organ bladder specimen. Polyclonal events were observed in five out of nine whole-organ mapping bladder cancers housing tumor associated normal urothelium, non-invasive urothelial lesions and CIS where different TERT promoter mutations were found compared to MIBC. The remaining four whole-organ mapping bladders were monoclonal for TERT mutations. No significant differences of telomere length were observed. Conclusions: Examining multiple whole-organ mapping bladders we conclude that TERT promoter mutations may be an early step in bladder cancer carcinogenesis as supported by TERT mutations detected in tumor associated normal urothelium as well as non-invasive urothelial lesions. Since mutated TERT promoter regions within non-invasive urothelial lesions are not sufficient alone for the establishment of cancerous growth, this points to the contribution of other gene mutations as a requirement for tumor development.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Clonality; TERT promoter mutation; Whole-organ mapping bladder tumor

TFE3 -rearranged Head and Neck Neoplasms : Twenty-two Cases Spanning the Morphologic Continuum Between Alveolar Soft Part Sarcoma and PEComa and Highlighting Genotypic Diversity. - Agaimy, Abbas; Michal, Michael; Abdelsatir, Ali; Abdelsatir, Azza A.; Abdulrahim, Sawsan; Laco, Jan; Ihrler, Stephan; Tögel, Lars; Stöhr, Robert; Bishop, Justin A.; Din, Nasir Ud; Michal, Michal (American Journal of Surgical Pathology, 2025)
TFE3 rearrangements characterize histogenetically, topographically, and biologically diverse neoplasms. Besides being a universal defining feature in alveolar soft part sarcoma (ASPS) and clear cell stromal tumor of the lung, TFE3 fusions have been reported in subsets of renal cell carcinoma, perivascular epithelioid cell tumor (PEComa), epithelioid hemangioendothelioma and ossifying fibromyxoid tumors. TFE3 -related neoplasms are rare in the head and neck and may pose diagnostic challenges. We herein describe 22 TFE3 fusion neoplasms affecting 11 males and 11 females aged 4 to 79 years (median, 25) and involving different head and neck sites: sinonasal cavities (n = 8), tongue (n = 4), oral cavity/oropharynx (n = 3), salivary glands (n = 2), orbit (n = 2), and soft tissue or unspecified sites (n = 3). Based on morphology and myomelanocytic immunophenotype, 10 tumors qualified as ASPS, 7 as PEComas (3 melanotic; all sinonasal), and 5 showed intermediate (indeterminate) histology overlapping with ASPS and PEComa. Immunohistochemistry for TFE3 was homogeneously strongly positive in all cases. Targeted RNA sequencing/FISH testing confirmed TFE3 fusions in 14 of 16 successfully tested cases (88%). ASPSCR1 was the most frequent fusion partner in ASPS (4 of 5 cases); one ASPS had a rare VCP::TFE3 fusion. The 6 successfully tested PEComas had known fusion partners as reported in renal cell carcinoma and PEComas ( NONO, PRCC, SFPQ , and PSPC1 ). The indeterminate tumors harbored ASPSCR1::TFE3 (n = 2) and U2AF2::TFE3 (n = 1) fusions, respectively. This large series devoted to TFE3-positive head and neck tumors illustrates the recently proposed morphologic overlap in the spectrum of TFE3 -associated mesenchymal neoplasms. While all PEComas were sinonasal, ASPS was never sinonasal and occurred in diverse head and neck sites with a predilection for the tongue. The indeterminate (PEComa-like) category is molecularly more akin to ASPS but shows different age, sex, and anatomic distribution compared with classic ASPS. We report VCP as a novel fusion partner in ASPS and PSPC1 as a novel TFE3 fusion partner in PEComa (detected in one PEComa). Future studies should shed light on the most appropriate terminological subtyping of these highly overlapping tumors.
EVALuna2:578182

Undifferentiated large cell/rhabdoid carcinoma presenting in the intestines of patients with concurrent or recent non-small cell lung cancer (NSCLC): clinicopathologic and molecular analysis of 14 cases indicates an unusual pattern of dedifferentiated metastases - Agaimy, Abbas; Daum, Ondrej; Michal, Michal; Schmidt, Mona W.; Stöhr, Robert; Hartmann, Arndt; Lauwers, Gregory Y. (Virchows Archiv, 2021)
Undifferentiated carcinoma metastatic to the bowel is uncommon in surgical pathology practice and might be confused with primary gastrointestinal carcinoma, melanoma, lymphoma, and others. We present 14 cases of uni- (n = 9) or multifocal (n = 5) undifferentiated large cell/rhabdoid carcinoma presenting in the bowel of patients with concurrent (n = 9) or recent (diagnosed 1 to 25 months earlier; median, 4) non-small cell lung cancer (NSCLC). Patients were 6 females and 8 males, aged 52 to 85 years. Primary NSCLC was verified histologically in 10 cases and by imaging in 4. The undifferentiated histology was present in the lung biopsy in 4/10 patients (as sole pattern in 3 and combined with adenocarcinoma in 1) and was limited to the intestinal metastases in the remainder. PDL1 was strongly expressed in 7/9 cases (CPS: 41 to 100). Loss of at least one SWI/SNF subunit was detected in 7/13 cases (54%). SMARCA2 loss (n = 6) was most frequent and was combined with SMARCA4 loss in one case. PBRM1 loss was observed in one tumor. Successful molecular testing of 11 cases revealed BRAF mutations in 4 (3 were non-V600E variants), KRAS mutations in 3, and wildtype in 4. None had EGFR mutations. Analysis of 4 paired samples revealed concordant KRAS (2) and BRAF (1) mutations or wildtype (1). Our study indicates that undifferentiated carcinoma within the intestines of patients with concurrent/recent NSCLC represents dedifferentiated metastasis from the NSCLC. Recognition of this unusual presentation is cardinal to avoid misdiagnosis with inappropriate therapeutic and prognostic implications.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Anaplastic carcinoma; Gastrointestinal; Intestine; Large cell carcinoma; Metastasis; NSCLC; Rhabdoid carcinoma; SMARCA4; SWI/SNF; Undifferentiated carcinoma

Uninflamed immunologic microenvironment of muscle-invasive bladder cancer associates with activating FGFR3 gene alterations. - Weyerer, Veronika; Stöhr, Robert; Strissel, Pamela; Strick, Reiner; Bolenz, Christian; Hartmann, Arndt; Erben, Philipp; Eckstein, Markus (CLINICAL CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2020-08-28

Variant morphology and random chromosomal integration of BK polyomavirus in posttransplant urothelial carcinomas - Bertz, Simone; Enßer, Armin; Stöhr, Robert; Eckstein, Markus; Apel, Hendrik; Mayr, Doris; Büttner-Herold, Maike; Gaisa, Nadine Therese; Comperat, Eva; Wullich, Bernd; Hartmann, Arndt; Knöll, Antje (Modern Pathology, 2020)
BK polyomavirus (BKPyV) causes major complications in solid organ transplant recipients but little is known about its role in the development of urothelial carcinoma (UC) during immunosuppression. Immunohistochemistry (IHC) screening for polyomavirus large T antigen (LTag) was performed in 94 micropapillary UC (MPUC), 480 unselected UC, 199 muscle invasive UC (including 83 UC with variant differentiation), 76 cases of plasmocytoid, nested and large nested UC and 15 posttransplant UC. LTag expressing UC were reevaluated regarding their histomorphological features and characterized by IHC for p53 and HER2, chromogenic in situ hybridization for HER2 and SNaPshot analysis of the TERT promoter and HRAS. Real-time PCR and next generation sequencing (NGS) were performed to search for BKPyV-DNA and for variants in the tumor and viral genomes. We detected five LTag expressing UC which were diagnosed between 2 and 18 years after kidney (n = 4) or heart (n = 1) transplantation. 89 MPUC without history of organ transplantation and overall 755 UC (including cases with variant histology) were LTag negative. Of the five LTag expressing UC, three were MPUC, one showed extensive divergent differentiation with Mullerian type clear cell carcinoma, and one displayed focal villoglandular differentiation. All five tumors had aberrant nuclear p53 expression, 2/5 were HER2-amplified, and 3/5 had TERT promoter mutations. Within the 50 most common cancer related genes altered in UC we detected very few alterations and no TP53 mutations. BKPyV-DNA was present in 5/5 UC, chromosomal integration of the BKPyV genome was detectable in 4/5 UC. Two UC with BKPyV integration showed small deletions in the BKPyV noncoding control region (NCCR). The only UC without detectable BKPyV integration had a high viral load of human herpesvirus 6 (HHV-6). Our results suggest that LTag expression of integrated BKPyV genomes and resulting p53 inactivation lead to aggressive high-grade UC with unusual, often micropapillary morphology.
CRIS-Team WoS Importer:2020-02-28

Xanthogranulomatous epithelial tumors/keratin-positive giant cell–rich tumors involving the head and neck: report of seven cases and review of the literature - Whaley, Rumeal D.; Agaimy, Abbas; Bridge, Julia A.; Stöhr, Robert; Din, Nasir Ud; Gagan, Jeffrey; Rampisela, Debby; Folpe, Andrew L.; Bishop, Justin A. (Virchows Archiv, 2024)
Xanthogranulomatous epithelial tumor (XGET) and HMGA2::NCOR2 fusion keratin-positive giant cell–rich tumor (KPGCT) are recently described morphologically overlapping rare neoplastic entities characterized by HMGA2::NCOR2 fusions, low-grade biological behavior, and a strong predilection for young females. To date, 47 cases have been reported with only four occurring in head and neck anatomic locations. In this study, we describe the clinicopathologic, immunohistochemical, and molecular findings of seven XGET/KPGCTs occurring in the head and neck region. The patients were six females and one male, aged 3.5–59 years old (median, 25 years). The tumors involved the ear, vocal cord, skull, neck soft tissue, and sinonasal cavity. Tumor sizes ranged from 1.5 to 6.7 cm. Histologically, the tumors were characterized by xanthogranulomatous histiocytes, osteoclast-like giant cells, and keratin-positive epithelioid cells. The XGET/KPGCTs involving the ear was remarkable for more cytologic atypia than previously described. Four cases had the HMGA2::NCOR2 fusion identified by NGS and three had HMGA2 gene locus alterations by FISH. Follow-up information was available for 3 of 7 patients (range 6–46 months). The patient with a vocal cord XGET/KPGCTs developed a local recurrence treated with excision. This study illustrates that XGET/KPGCTs involves the head and neck region as well, where it may be unexpected and hence under-recognized, and expands the anatomic locations of involvement to include unreported sites (ear, vocal cord, and sinonasal tract).
CRIS-Team Scopus Importer:2024-08-30
Keywords: HMGA2::NCOR2; Keratin-positive giant cell–rich tumor; KPGCT; Xanthogranulomatous epithelial tumor; XGET

YAP1-MAML2-Rearranged Poroid Squamous Cell Carcinoma (Squamoid Porocarcinoma) Presenting as a Primary Parotid Gland Tumor - Agaimy, Abbas; Stöhr, Robert; Tögel, Lars; Hartmann, Arndt; Cramer, Thomas (Head and Neck Pathology, 2020)
Porocarcinoma (synonym: malignant eccrine poroma) is a rare aggressive carcinoma type with terminal sweat gland duct differentiation. The squamous variant of porocarcinoma is even less frequent and might be indistinguishable from conventional squamous cell carcinoma (SCC). We herein describe the first case of a carcinoma presenting as a primary parotid gland malignancy in a 24-year-old male without any other primary tumor. Total parotidectomy and neck dissection were performed followed by adjuvant chemoradiation. The patient remained alive and well 10 months after diagnosis. Histology showed keratinizing SCC infiltrating extensively the parotid gland with subtle poroid cell features. Oncogenic HPV infection was excluded by DNA-based testing. NGS analysis using the TruSight RNA fusion panel (Illumina) revealed a novel YAP1-MAML2 gene fusion. This gene fusion was reported recently in a subset of cutaneous porocarcinoma and poroma. This case of poroid SCC (or squamoid porocarcinoma) adds to the differential diagnosis of SCC presenting as parotid gland tumor and highlights the value of molecular testing in cases with unusual presentation.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Head and neck; MAML2; Parotid; Porocarcinoma; Poroma; Salivary glands; Squamous cell carcinoma; YAP1